Slow-release antibacterial reinforced composite film for fresh keeping of fruits and vegetables and preparation method of slow-release antibacterial reinforced composite film

Through sulfonation and quaternization modification treatment of nanocellulose, combined with curcumin and other materials, a sustained-release inhibitory enhancement composite film with excellent barrier, antibacterial and mechanical properties was prepared, which solved the problems of limited antibacterial effect and poor mechanical properties of the existing films, and achieved efficient preservation of fruits and vegetables.

CN119552398AInactive Publication Date: 2025-03-04中科纳美(天津)生物工程有限公司 +1

Patent Information

Application Number
CN202510127496.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the preparation and application of existing sustained-release antibacterial films, there are problems such as limited antibacterial effect, unstable sustained-release performance and poor mechanical properties, which are difficult to meet the needs of preservation of fruits and vegetables.

Method used

Nanocellulose was treated with sulfonated and quaternized modification, combined with curcumin, gelatin, sodium carboxymethylcellulose and carboxymethyl chitosan and other materials, and prepared a sustained-release inhibitory and enhanced composite film with excellent barrier, antibacterial and mechanical properties.

Benefits of technology

Significantly extend the shelf life of fruits and vegetables, improve the safety and quality of food, and reduce food waste and losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552398A_ABST
    Figure CN119552398A_ABST
Patent Text Reader

Abstract

The invention provides a slow-release antibacterial enhanced composite film for fruit and vegetable preservation and a preparation method thereof, and the preparation method comprises the following steps: performing sulfonation modification treatment on nano cellulose powder to obtain sulfonated nano cellulose; carrying out quaternization modification treatment on the sulfonated nano-crystalline cellulose to obtain quaternary ammonium sulfonated nano-crystalline cellulose; adding gelatin and sodium carboxymethyl cellulose into deionized water to obtain a wall material solution, and adding curcumin into the wall material solution to obtain a prepolymer solution; stirring and emulsifying the prepolymer solution at a high speed to obtain a prepolymer suspension; adding a chitosan solution into the prepolymer suspension to obtain a microcapsule solution, adding tannic acid into the microcapsule solution to obtain a microcapsule suspension, and performing spray drying to obtain double-layer microcapsule powder; the preparation method comprises the following steps: uniformly mixing polylactic acid, quaternary ammonium sulfonated nanocellulose, the double-layer microcapsule powder, a plasticizer, a lubricant and an antioxidant to obtain a mixed material, and sequentially carrying out melt extrusion, cooling, pelletizing and film blowing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fruit and vegetable preservation, and relates to a slow-release antibacterial enhanced composite film for fruit and vegetable preservation and a preparation method thereof. Background Art

[0002] Fruits and vegetables are an indispensable part of people's daily diet, and their freshness and quality are directly related to consumers' health and satisfaction. However, during the storage and transportation of fruits and vegetables after picking, it is often difficult to maintain their original freshness and nutritional value due to factors such as the growth of microorganisms, nutrient loss caused by respiration, and physical damage. Therefore, the development of efficient fruit and vegetable preservation technology has always been an important research direction in the field of food science and agriculture.

[0003] Traditional methods of preserving fruits and vegetables mainly include low-temperature refrigeration, modified atmosphere packaging and chemical preservatives. Low-temperature refrigeration slows down the respiration of fruits and vegetables and the growth of microorganisms by lowering the temperature, but long-term low temperature may cause the texture and taste of fruits and vegetables to deteriorate. Modified atmosphere packaging inhibits the respiration and microbial activity of fruits and vegetables by adjusting the gas composition in the package (such as oxygen, carbon dioxide and nitrogen), but this method has high requirements for packaging materials and equipment and is not suitable for all types of fruits and vegetables. Although chemical preservatives can effectively inhibit the growth of microorganisms, long-term consumption of fruits and vegetables containing chemical preservatives may have a negative impact on human health.

[0004] In order to overcome the shortcomings of traditional preservation methods, researchers have begun to explore the use of natural and environmentally friendly preservation materials and technologies in recent years. Among them, slow-release antibacterial films have attracted widespread attention because they can form a protective layer on the surface of fruits and vegetables and inhibit the growth of microorganisms by slowly releasing antibacterial substances. This type of film is usually composed of natural polymer materials (such as chitosan, starch, cellulose, etc.) and antibacterial substances (such as plant essential oils, organic acids, nanosilver, etc.), and has good biocompatibility and degradability.

[0005] However, there are still some problems in the preparation and application of existing sustained-release antibacterial films. First, the composition and preparation process of the film have an important influence on the antibacterial effect and sustained-release performance. At present, the antibacterial substance loading of many sustained-release antibacterial films is low, resulting in limited antibacterial effect; at the same time, the instability of the sustained-release performance also affects the preservation effect of the film. Secondly, the mechanical properties of the film are also an important factor affecting its application. Due to improper material selection or unreasonable process parameters in the preparation process of some films, the mechanical properties such as toughness, tensile strength and tear strength of the film are poor, which is difficult to meet the needs of practical applications. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables and a preparation method thereof. The composite film prepared by the present invention has excellent barrier properties, antibacterial properties and mechanical properties. Using it for fruit and vegetable packaging can significantly extend the shelf life of fruits and vegetables and reduce food waste and loss.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables, the preparation method comprising:

[0009] (I) sulfonating and modifying nanocellulose powder with 1,3-propane sultone to obtain sulfonated nanocellulose; then quaternizing and modifying the sulfonated nanocellulose with octadecyltrimethylammonium chloride to obtain quaternary ammonium sulfonated nanocellulose;

[0010] (II) adding gelatin and sodium carboxymethyl cellulose into deionized water, mixing, stirring and heating to obtain a wall material solution, adding curcumin to the wall material solution to obtain a prepolymer solution; subjecting the prepolymer solution to high-speed stirring and emulsification, then dropping an acetic acid solution into the prepolymer solution under stirring and water bath heating conditions to adjust the pH value thereof, and cooling in an ice water bath to obtain a prepolymer suspension;

[0011] (III) dispersing carboxymethyl chitosan in an acetic acid solution to obtain a chitosan solution, adding the chitosan solution to the prepolymer suspension, mixing uniformly to obtain a microcapsule solution, adding an alkali solution to the microcapsule solution to adjust the pH value thereof, then adding tannic acid to the microcapsule solution, mixing uniformly to obtain a microcapsule suspension, and spray drying the microcapsule suspension to obtain a double-layer microcapsule powder;

[0012] (IV) Polylactic acid, the quaternary ammonium sulfonated nanocellulose obtained in step (I), the double-layer microcapsule powder obtained in step (III), a plasticizer, a lubricant and an antioxidant are uniformly mixed to obtain a mixed material, and the mixed material is sequentially melt-extruded, cooled, pelletized and film-blown to obtain the sustained-release antibacterial enhanced composite film.

[0013] The sustained-release antibacterial enhanced composite film prepared by the present invention has excellent barrier properties, antibacterial properties and mechanical properties, and has great application potential in the field of fruit and vegetable preservation. First, the present invention improves the dispersibility and compatibility of nanocellulose in the polymer matrix by sulfonation and quaternization modification, thereby enhancing the mechanical properties and barrier properties of the composite film. Subsequently, the present invention uses curcumin as the core material and gelatin and sodium carboxymethyl cellulose as the wall material to prepare a single-layer microcapsule with a core-shell structure, and then uses carboxymethyl chitosan to perform secondary coating and reinforcement on the single-layer microcapsule, and utilizes electrostatic action and intermolecular force to form a carboxymethyl chitosan protective layer on the surface of the single-layer microcapsule, which can increase the film thickness on the surface of curcumin to better resist external adverse factors and reduce the environmental sensitivity of the double-layer microcapsule. Finally, quaternary ammonium sulfonated nanocellulose and double-layer microcapsule powder were added to the polylactic acid matrix, and a composite film was obtained after melt extrusion, cooling, pelletizing and film blowing. The synergistic effect of quaternary ammonium sulfonated nanocellulose and double-layer microcapsule powder significantly improved the barrier properties, antibacterial properties and mechanical properties of the composite film.

[0014] The synergistic effect of quaternary ammonium sulfonated nanocellulose and double-layer microcapsule powder is mainly reflected in the following aspects: on the one hand, the tight network structure formed by quaternary ammonium sulfonated nanocellulose in the composite film provides a good attachment basis for the double-layer microcapsule powder. This structural synergy not only enhances the overall mechanical properties of the composite film, but also enables the double-layer microcapsule powder to be more evenly distributed in the composite film, thereby improving the release efficiency and antibacterial effect of curcumin. On the other hand, the gas barrier effect of quaternary ammonium sulfonated nanocellulose and the antibacterial properties of the double-layer microcapsule powder complement each other and jointly improve the preservation effect of the composite film. Quaternary ammonium sulfonated nanocellulose reduces the damage of external gases to fruits and vegetables, while the double-layer microcapsule powder inhibits the growth of microorganisms by slowly releasing curcumin. The synergistic effect of the two provides all-round preservation protection for fruits and vegetables.

[0015] Nanocellulose is one of the most abundant natural polymers. It has the advantages of wide source, renewable, biodegradable, good biocompatibility and green environmental protection. In addition, it has excellent mechanical properties, high specific surface area, low density and good thermal stability. It is an excellent nano-reinforced filler. The tensile strength, elastic modulus, thermal stability and barrier properties of the composite film can be significantly improved by adding nanocellulose to the polymer matrix. However, there are a large number of hydroxyl functional groups on the surface of nanocellulose, which hinders its compatibility and dispersibility in the polymer matrix and limits the further enhancement of the performance of the composite film. Therefore, it is necessary to hydrophobically modify nanocellulose and reduce its hydrophilicity, so as to improve the compatibility and dispersibility of nanocellulose in the polymer matrix. In addition, in order to give the composite film excellent antibacterial properties, it is necessary to consider the compatibility of the antibacterial agent in the composite material system to avoid the negative impact of the addition of the antibacterial agent on the performance of the composite film.

[0016] In order to solve the problem that the hydrophilic nanocellulose is dispersible in the hydrophobic polymer matrix and the nanocellulose lacks antibacterial activity, the present invention adopts sulfonation and quaternary ammonium salt adsorption combined modification to treat the nanocellulose, so that the surface properties of the nanocellulose are optimized, not only the hydrophilicity of the nanocellulose is reduced, but also its compatibility and dispersibility with the polymer matrix are improved, and more polar functional groups are introduced, which is conducive to forming stronger interfacial interactions. At the same time, the modified nanocellulose also gives the composite film excellent mechanical properties, and the quaternary ammonium sulfonated nanocellulose forms a continuous network structure in the composite film, which effectively improves the tensile strength and toughness of the composite film.

[0017] Among the numerous organic antimicrobial modifiers, quaternary ammonium antimicrobial agents have the advantages of broad-spectrum antimicrobial activity, low toxicity, low price, and good environmental stability. The bactericidal mechanism is as follows: the quaternary ammonium cationic functional group adsorbs the negatively charged bacterial cell membrane on the surface through electrostatic action, and then the long alkane chain of the quaternary ammonium salt enters the phospholipid bilayer of the cell membrane, interfering with the normal metabolism of the bacterial cells, and ultimately leading to bacterial cell lysis to achieve the bactericidal and antibacterial effects. Due to the electrostatic adsorption mechanism of quaternary ammonium salts in the antibacterial process, it can widely act on the negatively charged bacterial surface rather than specifically bind to kill bacteria, and thus can effectively avoid the risk of increased bacterial resistance.

[0018] Since polymer quaternary ammonium salts have more action sites and higher charge density, they are more conducive to the electrostatic adsorption effect, and the adsorption effect between bacteria is faster and stronger; however, too large a molecular weight will also affect the contact of quaternary ammonium salt molecules with the bacterial surface to play a role, which will lead to a weakening of antibacterial activity. The present invention uses octadecyl trimethyl ammonium chloride as an organic antibacterial agent, and uses physical electrostatic adsorption to load octadecyl trimethyl ammonium chloride onto nanocellulose, while satisfying the hydrophobic modification and antibacterial modification of nanocellulose. However, the loading amount of nanocellulose on octadecyl trimethyl ammonium chloride depends on the anion content on its surface. In order to increase the loading amount of octadecyl trimethyl ammonium chloride, the present invention first sulfonates the nanocellulose by 1,3-propane sultone. The sulfonation modification can provide rich and stable anion sites for the surface of nanocellulose, which is conducive to improving the adsorption of nanocellulose on octadecyl trimethyl ammonium chloride.

[0019] The present invention uses curcumin as the main antibacterial material in the composite film. As a highly efficient bioactive ingredient, curcumin has multiple biological activities such as anti-oxidation, anti-inflammatory and anti-tumor. However, curcumin has poor water solubility and unstable chemical properties. It is easily degraded by factors such as light, heat, acid and alkali, which greatly limits its application in composite films. The present invention can encapsulate curcumin in a stable wall material through microencapsulation technology, thereby improving its stability and bioavailability; at the same time, the microencapsulation technology can also protect curcumin from damage by the external environment, such as the influence of factors such as oxygen, humidity and temperature, thereby extending its storage stability.

[0020] The present invention uses curcumin as the core material and gelatin and sodium carboxymethyl cellulose as the wall material to prepare a single-layer microcapsule. Gelatin is a protein obtained by hydrolyzing collagen in connective tissues such as animal skin and bones. It has good film-forming properties, biodegradability and biocompatibility. The isoelectric point of gelatin is about pH=5, which means that when the pH value is lower than 5, gelatin is positively charged; and when the pH value is higher than 5, gelatin is negatively charged. Sodium carboxymethyl cellulose is a water-soluble anionic polysaccharide obtained by chemically modifying cellulose. It contains negatively charged carboxyl functional groups, so it always carries a negative charge in an aqueous solution. The present invention adjusts the pH value of the reaction system to below 5 so that gelatin is positively charged, and utilizes the positively charged gelatin and the negatively charged sodium carboxymethyl cellulose to neutralize charges under a specific pH value environment, so that the solubility is reduced and phase separation is formed, which promotes them to aggregate and deposit around curcumin to form a complex coacervate coated around the curcumin, and finally obtains a single-layer microcapsule with a stable core-shell structure, wherein curcumin as a core material is wrapped inside the complex coacervate formed by gelatin and sodium carboxymethyl cellulose, and the complex coacervate as an outer shell has a certain thickness and mechanical strength, and can protect the curcumin from the influence of the external environment.

[0021] In order to further improve the environmental stability, thermal stability and sustained release effect of the microcapsules, the present invention further coats the surface of the single-layer microcapsules with a carboxymethyl chitosan protective layer, which has the following functions:

[0022] On the one hand, the carboxymethyl chitosan protective layer significantly improves the environmental stability of the double-layer microcapsules and reduces the volatilization and degradation of curcumin during storage and transportation. This is because, as a chitosan derivative, the charge properties of carboxymethyl chitosan depend on its chemical structure and environmental pH. The carboxymethyl chitosan molecule contains negatively charged carboxyl groups (-COOH) and positively charged amine groups (-NH2). Under acidic conditions, the amine groups of carboxymethyl chitosan will be protonated and positively charged; under alkaline conditions, the carboxyl groups will be ionized and negatively charged. Therefore, carboxymethyl chitosan can present different charge states in solution, depending on the pH value of the solution. The present invention adjusts the pH value of the reaction system to weak acidity so that the carboxymethyl chitosan is positively charged, and the positively charged carboxymethyl chitosan is tightly combined with the negatively charged complex coacervate through electrostatic interaction to form a stable double-layer shell structure. The electrostatic combination not only enhances the compactness of the wall material, but also effectively isolates the adverse effects of the external environment on curcumin, such as pH value changes, ionic strength fluctuations and temperature changes, thereby significantly improving the environmental stability of the double-layer microcapsules.

[0023] On the other hand, the carboxymethyl chitosan protective layer significantly improves the thermal stability of the double-layer microcapsules. This is because the melting point of carboxymethyl chitosan is high and it is not easy to decompose at high temperatures. In the double-layer microcapsules, the introduction of the carboxymethyl chitosan protective layer effectively improves the overall thermal stability of the double-layer microcapsules. When the double-layer microcapsules are in a high-temperature environment, the carboxymethyl chitosan protective layer can be tightly wrapped on the surface of the complex coacervate layer to prevent curcumin from being quickly released due to heat. At the same time, the thermal shrinkage of the carboxymethyl chitosan protective layer enables it to form a denser barrier in a high-temperature environment, further enhancing the thermal stability of the double-layer microcapsules. In addition, the addition of the carboxymethyl chitosan protective layer increases the thickness and density of the microcapsule wall, effectively preventing the volatilization of curcumin and the decomposition of the wall material at high temperatures, and effectively slowing down the release of curcumin in water, maintaining the stability of the microcapsule structure.

[0024] On the other hand, the presence of the carboxymethyl chitosan protective layer significantly slows down the release rate of curcumin, achieving stable delivery and sustained release of curcumin. This is because the carboxymethyl chitosan protective layer has a certain permeability and can control the speed at which curcumin molecules pass through, thereby achieving a sustained release effect. By adjusting the thickness and molecular structure of the carboxymethyl chitosan protective layer, precise control of the release rate of curcumin can be achieved.

[0025] As a preferred technical solution of the present invention, in step (I), the sulfonated nanocellulose is prepared by the following method:

[0026] The nanocellulose powder is added into a sodium hydroxide solution, and a nanocellulose dispersion is obtained after ultrasonic dispersion, and then the nanocellulose dispersion is mixed, stirred and heated to obtain a nanocellulose suspension; a 1,3-propane sultone solution is added into the nanocellulose suspension, and the mixture is mixed, stirred and heated to react, and a reaction product is obtained after the reaction is completed, and a hydrochloric acid solution is dripped into the reaction product to adjust its pH value, and then the reaction product is dialyzed and freeze-dried to obtain the sulfonated nanocellulose.

[0027] In some optional examples, the mass fraction of the sodium hydroxide solution is 5-10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In some optional examples, the ratio of the nanocellulose powder to the sodium hydroxide solution is 1g:(50~60)mL, for example, it can be 1g:50mL, 1g:51mL, 1g:52mL, 1g:53mL, 1g:54mL, 1g:55mL, 1g:56mL, 1g:57mL, 1g:58mL, 1g:59mL or 1g:60mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In some optional examples, the ultrasonic power of the ultrasonic dispersion of the nanocellulose powder and the sodium hydroxide solution is 300-400 W, for example, 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W or 400 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In some optional examples, the ultrasonic dispersion time of the nanocellulose powder and the sodium hydroxide solution is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] In some optional examples, the mixing and stirring time of the nanocellulose dispersion is 3 to 5 hours, for example, it can be 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In some optional examples, the heating temperature during mixing and stirring of the nanocellulose dispersion is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional examples, the 1,3-propane sultone solution consists of 1,3-propane sultone and dimethyl sulfoxide.

[0034] In some optional examples, the mass fraction of 1,3-propane sultone in the 1,3-propane sultone solution is 4-5wt%, for example, 4.0wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt% or 5.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional examples, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone is 1:(0.14~0.15), for example, it can be 1:0.14, 1:0.141, 1:0.142, 1:0.143, 1:0.144, 1:0.145, 1:0.146, 1:0.147, 1:0.148, 1:0.149 or 1:0.15, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] The present invention particularly limits the mass ratio of nanocellulose powder to 1,3-propane sultone in the nanocellulose suspension to 1:(0.14-0.15). When the amount of 1,3-propane sultone used is lower than the lower limit of the range defined by the present invention, the number of sulfonic acid functional groups on the surface of the nanocellulose is too small, and the sulfonation modification is insufficient, thereby affecting the number of anion sites on the surface of the nanocellulose, resulting in a decrease in its adsorption capacity for octadecyltrimethylammonium chloride; in addition, the sulfonic acid functional groups serve as molecular bridges connecting the nanocellulose and octadecyltrimethylammonium chloride, and their insufficient number will directly affect the effect of quaternary ammonium modification, resulting in uneven distribution of octadecyltrimethylammonium chloride on the surface of the nanocellulose and a decrease in the grafting rate, which ultimately affects the antibacterial and mechanical properties of the quaternary ammonium sulfonated nanocellulose.

[0037] When the amount of 1,3-propane sultone exceeds the upper limit of the range defined by the present invention, it will cause excessive sulfonation of nanocellulose, causing significant changes in the chemical structure and physical properties of sulfonated nanocellulose, and the chain structure of sulfonated nanocellulose will break due to excessive reaction, resulting in a decrease in its strength, rigidity and stability. In addition, excessive sulfonation will also affect the subsequent quaternization modification effect, because, on the one hand, the sulfonic acid functional groups on the surface of sulfonated nanocellulose are limited in number as adsorption sites, and when the amount of 1,3-propane sultone is increased, although more sulfonic acid functional groups are introduced, the excessive amount of 1,3-propane sultone will lead to saturation of adsorption sites, and the part exceeding the carrying capacity of the surface of sulfonated nanocellulose will not be able to effectively participate in the subsequent quaternization reaction. On the other hand, during the quaternization process, octadecyltrimethylammonium chloride needs to be adsorbed on the sulfonic acid functional groups on the surface of sulfonated nanocellulose. When the dosage of 1,3-propane sultone is too high, it will lead to uneven distribution of sulfonic acid functional groups, which will in turn cause uneven distribution of octadecyltrimethylammonium chloride on the surface of sulfonated nanocellulose, affecting the performance of the final product.

[0038] In some optional examples, the mixing and stirring time of the nanocellulose suspension and the 1,3-propane sultone solution is 5 to 6 hours, for example, it can be 5.0 hours, 5.1 hours, 5.2 hours, 5.3 hours, 5.4 hours, 5.5 hours, 5.6 hours, 5.7 hours, 5.8 hours, 5.9 hours or 6.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In some optional examples, the heating temperature when the nanocellulose suspension and the 1,3-propane sultone solution are mixed and stirred is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In some optional instances, the mass fraction of the hydrochloric acid solution is 5~10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] In some optional embodiments, hydrochloric acid solution is added dropwise to the reaction product to adjust its pH value to 1-2, for example, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In some optional examples, the molecular weight cutoff of the dialysis bag used in the dialysis is 10,000~20,000Da, for example, it can be 10,000Da, 11,000Da, 12,000Da, 13,000Da, 14,000Da, 15,000Da, 16,000Da, 17,000Da, 18,000Da, 19,000Da or 20,000Da, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In some optional examples, the dialysis time is 2 to 3 days.

[0044] In some optional embodiments, the freeze-drying temperature is -60~-70°C, for example, it can be -60°C, -61°C, -62°C, -63°C, -64°C, -65°C, -66°C, -67°C, -68°C, -69°C or -70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] In some optional embodiments, the freeze-drying time is 6 to 12 hours, for example, it can be 6.0 h, 6.5 h, 7.0 h, 7.5 h, 8.0 h, 8.5 h, 9.0 h, 9.5 h, 10.0 h, 10.5 h, 11.0 h, 11.5 h or 12.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] As a preferred technical solution of the present invention, in step (I), the quaternary ammonium sulfonated nanocellulose is prepared by the following method:

[0047] The sulfonated nanocellulose is added to isopropanol to obtain a sulfonated nanocellulose suspension after ultrasonic dispersion, an alkali solution is added dropwise to the sulfonated nanocellulose suspension to adjust its pH value, and then octadecyltrimethylammonium chloride is added to the sulfonated nanocellulose suspension, mixed and stirred and heated for a period of time, and then the heating is stopped, and the mixing and stirring is continued at room temperature for a period of time to obtain a reaction product, and the reaction product is dialyzed and freeze-dried to obtain the quaternary ammonium sulfonated nanocellulose.

[0048] The presence of isopropanol can increase the disorder of sulfonated nanocellulose and reduce the possibility of hydrogen bond formation and cross-linking, so that the sulfonated nanocellulose maintains a larger specific surface area, which is beneficial to the quaternary ammonium cationic modification reaction of sulfonated nanocellulose. At the same time, the use of isopropanol can destroy the crystal structure of sulfonated nanocellulose to a large extent, so that the quaternary ammonium modification reaction can proceed more fully.

[0049] In some optional examples, the ratio of the sulfonated nanocellulose to isopropanol is 1g:(30~40)mL, for example, it can be 1g:30mL, 1g:31mL, 1g:32mL, 1g:33mL, 1g:34mL, 1g:35mL, 1g:36mL, 1g:37mL, 1g:38mL, 1g:39mL or 1g:40mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional examples, the ultrasonic power of the ultrasonic dispersion of the sulfonated nanocellulose and isopropanol is 300-400 W, for example, 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W or 400 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In some optional examples, the ultrasonic dispersion time of the sulfonated nanocellulose and isopropanol is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] In some optional examples, the concentration of the alkali solution is 0.5~1.5mol / L, for example, it can be 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L or 1.5mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In some optional embodiments, an alkali solution is added to the sulfonated nanocellulose suspension to adjust its pH value to 9-10, for example, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9 or 10.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In some optional examples, the mass ratio of the sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension is 1:(0.2~0.3), for example, it can be 1:0.2, 1:0.21, 1:0.22, 1:0.23, 1:0.24, 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29 or 1:0.3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] The present invention particularly limits the mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension to 1:(0.2-0.3). When the amount of octadecyltrimethylammonium chloride used is lower than the lower limit of the range defined by the present invention, the coverage of octadecyltrimethylammonium chloride on the surface of sulfonated nanocellulose is insufficient. The antibacterial effect of octadecyltrimethylammonium chloride mainly depends on the interaction between its positive charge and the negative charge of the bacterial cell membrane, thereby destroying the integrity of the bacterial cell membrane. If the coverage of octadecyltrimethylammonium chloride is insufficient, the chance of octadecyltrimethylammonium chloride contacting with the bacterial cell membrane is reduced, resulting in decreased antibacterial performance of the product. In addition, as a cationic surfactant, octadecyltrimethylammonium chloride has a significant hydrophobic property in its long-chain alkyl part. When octadecyltrimethylammonium chloride is combined with sulfonated nanocellulose, the hydrophobic alkyl chains of the quaternary ammonium salt tend to be arranged in a direction away from water molecules, thereby forming a hydrophobic barrier on the surface of nanocellulose. This barrier can effectively prevent the penetration of water molecules and improve the hydrophobic properties of the material. When the amount of octadecyltrimethylammonium chloride is too small, the number of hydrophobic alkyl chains is limited and a complete hydrophobic barrier cannot be formed, resulting in insufficient hydrophobicity of the product, which in turn affects its compatibility and dispersibility with the polylactic acid matrix.

[0056] Increasing the amount of octadecyltrimethylammonium chloride can increase the positive charge density on the surface of sulfonated nanocellulose, thereby enhancing the antibacterial properties of the product. However, when the amount of octadecyltrimethylammonium chloride exceeds the upper limit of the range defined in the present invention, the hydrophobic modification of the surface of the sulfonated nanocellulose is close to saturation. Continuing to increase the amount of octadecyltrimethylammonium chloride cannot further increase the number of hydrophobic alkyl chains. Instead, it may cause the product surface to be too rough or form an uneven hydrophobic layer, affecting the overall performance of the product.

[0057] In some optional examples, the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride are mixed and stirred under heating conditions for 3 to 4 hours, for example, 3.0 hours, 3.1 hours, 3.2 hours, 3.3 hours, 3.4 hours, 3.5 hours, 3.6 hours, 3.7 hours, 3.8 hours, 3.9 hours or 4.0 hours, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] In some optional examples, the heating temperature when the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride are mixed and stirred under heating conditions is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] In some optional examples, the mixing and stirring time of the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride at room temperature is 10 to 15 hours, for example, it can be 10.0 hours, 10.5 hours, 11.0 hours, 11.5 hours, 12.0 hours, 12.5 hours, 13.0 hours, 13.5 hours, 14.0 hours, 14.5 hours or 15.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] In some optional examples, the molecular weight cutoff of the dialysis bag used in the dialysis is 10,000~20,000Da, for example, it can be 10,000Da, 11,000Da, 12,000Da, 13,000Da, 14,000Da, 15,000Da, 16,000Da, 17,000Da, 18,000Da, 19,000Da or 20,000Da, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] In some optional examples, the dialysis time is 5 to 8 days, for example, 5 days, 6 days, 7 days or 8 days, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In some optional embodiments, the freeze-drying temperature is -40~-50°C, for example, it can be -40°C, -41°C, -42°C, -43°C, -44°C, -45°C, -46°C, -47°C, -48°C, -49°C or -50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] In some optional embodiments, the freeze-drying time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] As a preferred technical solution of the present invention, in step (II), the concentration of gelatin and sodium carboxymethyl cellulose in the wall material solution is 15-20 g / L, for example, it can be 15 g / L, 15.5 g / L, 16 g / L, 16.5 g / L, 17 g / L, 17.5 g / L, 18 g / L, 18.5 g / L, 19 g / L, 19.5 g / L or 20 g / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0065] In some optional examples, the mass ratio of the gelatin to the sodium carboxymethyl cellulose is (6-7):1, for example, it can be 6.0:1, 6.1:1, 6.2:1, 6.3:1, 6.4:1, 6.5:1, 6.6:1, 6.7:1, 6.8:1, 6.9:1 or 7.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] In the process of preparing single-layer microcapsules, the mass ratio of gelatin to sodium carboxymethyl cellulose has a crucial influence on the thermal stability of single-layer microcapsules, the sustained release effect of curcumin, and the embedding rate. The collagen chains in gelatin hydrogen bond with the hydroxyl and carboxymethyl groups in sodium carboxymethyl cellulose, which enhances the cohesion of the capsule wall material and forms a tight and uniform capsule wall structure. This tight capsule wall structure can effectively prevent the rapid transfer of heat, so that the microcapsules can maintain structural integrity when heated, thereby delaying the decomposition or leakage of internal curcumin.

[0067] The present invention further defines the mass ratio of gelatin to sodium carboxymethyl cellulose as (6-7):1. When the mass ratio of gelatin to sodium carboxymethyl cellulose is controlled within this mass range, the two can work synergistically to form a capsule wall structure with ideal sustained-release performance. The water-absorbing and swelling properties of gelatin enable the capsule wall to gradually soften and swell in water, forming a dense gel layer, thereby slowing down the release rate of curcumin. The viscosity and gelling properties of sodium carboxymethyl cellulose can increase the viscosity inside the capsule wall, further extending the release time. This synergistic effect enables the microcapsule to maintain a stable release rate over a long period of time, meeting the sustained-release requirements for curcumin.

[0068] When the amount of gelatin used exceeds the upper limit of the range defined in the present invention, the proportion of gelatin in the capsule wall increases, which will cause the capsule wall material to become too soft and easy to deform, reducing the thermal stability of the microcapsule. Under heating conditions, the capsule wall is more likely to change shape or even rupture, causing the curcumin wrapped inside to leak. In addition, when the amount of gelatin used is too high, the swelling property of the capsule wall is too strong, causing a large amount of curcumin to be released in a short period of time, thereby losing the sustained-release effect; at the same time, too much gelatin will also increase the permeability of the capsule wall, making it easier for water to enter the capsule, accelerating the dissolution and release of curcumin. In addition, when the amount of gelatin used is too high, the capsule wall material will become too viscous and difficult to disperse, making it difficult for curcumin to be evenly wrapped inside the capsule wall, thereby reducing the embedding rate of curcumin.

[0069] On the contrary, when the amount of gelatin is lower than the lower limit of the range defined in the present invention, the proportion of sodium carboxymethyl cellulose in the capsule wall is relatively too high. Although the rigidity and stability of the capsule wall can be improved, the capsule wall material will become too hard and brittle, and it is easy to be mechanically damaged during processing or storage, which not only affects the thermal stability of the microcapsules, but also causes curcumin to leak from the capsule wall, thereby reducing the embedding rate of curcumin. In addition, when the amount of gelatin is too low, the swelling performance of the capsule wall is insufficient, and an effective gel layer cannot be formed to control the release rate of curcumin, resulting in curcumin being released into the external environment at a faster rate, and the ideal sustained release effect cannot be achieved.

[0070] In some optional examples, the mixing and stirring time is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] In some optional embodiments, the heating temperature during mixing and stirring is 40-50°C, for example, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] In some optional examples, the ratio of the total mass of gelatin and sodium carboxymethyl cellulose in the wall material solution to the mass of the curcumin is (4-5):1, for example, 4.0:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1 or 5.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] In some optional examples, the stirring speed of the high-speed stirring emulsification of the prepolymer solution is 8000~10000rpm, for example, it can be 8000rpm, 8200rpm, 8400rpm, 8600rpm, 8800rpm, 9000rpm, 9200rpm, 9400rpm, 9600rpm, 9800rpm or 10000rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0074] In some optional examples, the high-speed stirring emulsification time of the prepolymer solution is 3 to 5 minutes, for example, it can be 3.0 minutes, 3.2 minutes, 3.4 minutes, 3.6 minutes, 3.8 minutes, 4.0 minutes, 4.2 minutes, 4.4 minutes, 4.6 minutes, 4.8 minutes or 5.0 minutes, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0075] In some optional embodiments, the stirring speed during the process of dripping the acetic acid solution is 300~400rpm, for example, it can be 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm, 360rpm, 370rpm, 380rpm, 390rpm or 400rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0076] In some optional embodiments, the temperature of the water bath heating during the process of dripping the acetic acid solution is 40-50°C, for example, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0077] In some optional examples, the acetic acid solution is added dropwise to the prepolymer solution to adjust its pH value to 4-5, for example, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9 or 5.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0078] The present invention specifically limits the addition of acetic acid solution to the prepolymer solution to adjust its pH value to 4-5. As the pH value of the prepolymer solution decreases, the electrostatic repulsion between gelatin and sodium carboxymethyl cellulose decreases, and the particle size of the formed single-layer microcapsules gradually increases. When the pH value of the prepolymer solution drops below 4, the particle size of the microcapsules is too large and can no longer maintain a good spherical dispersion state, and they begin to adhere to each other. However, when the pH value of the prepolymer solution exceeds 5, although microcapsules with a good spherical dispersion state can be obtained, the particle size of the obtained microcapsules is too small, which leads to a too low embedding amount of curcumin, affecting the sustained-release antibacterial effect of curcumin. Therefore, in order to take into account the spherical dispersion state and large particle size of the microcapsules, the present invention specifically limits the pH value of the prepolymer solution to 4-5.

[0079] In some optional embodiments, the temperature of the ice water bath is 5-15°C, for example, it can be 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, 11°C, 12°C, 13°C, 14°C or 15°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0080] In some optional examples, the cooling in the ice water bath is 1 to 2 hours, for example, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0081] In some optional examples, the mixing and stirring is continued for 20 to 30 minutes after cooling to obtain the prepolymer suspension, for example, it can be 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes or 30 minutes, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0082] As a preferred technical solution of the present invention, in step (III), the carboxymethyl chitosan is prepared by the following method:

[0083] Chitosan powder is mixed with sodium hydroxide and then ball-milled once to obtain a mixture, sodium chloroacetate and sodium iodide are added to the mixture, and then ball-milled twice to obtain a solid product, the solid product is uniformly mixed with deionized water to obtain a product solution, and a hydrochloric acid solution is added to the product solution to adjust the pH value of the product solution to 7; then, the product solution is filtered, washed and dried to obtain the carboxymethyl chitosan.

[0084] Chitosan is mainly composed of random copolymerization of N-acetylglucosamine and glucosamine units. The particularity of this structure gives chitosan a series of significant functional properties, such as excellent biocompatibility, non-toxicity, good biodegradability and antibacterial activity, but unmodified chitosan is only water-soluble and antibacterial under acidic conditions, which limits its scope of application. The present invention uses sodium chloroacetate to carboxymethylate chitosan, aiming to introduce hydrophilic carboxymethyl functional groups, thereby improving the water solubility and reactivity of chitosan. Compared with chitosan, carboxymethyl chitosan not only retains the original biocompatibility and degradability of chitosan, but also gives it certain antibacterial and reactivity.

[0085] The present invention uses sodium chloroacetate as a carboxymethyl modification agent and sodium iodide as a catalyst, and adopts a mechanochemical method to induce a chemical reaction, thereby introducing a carboxymethyl functional group on the chitosan molecular chain, and the introduction of the carboxymethyl functional group greatly improves the solubility of chitosan. The present invention adopts mechanical ball milling to promote the alkalization reaction and the carboxymethylation reaction. During the ball milling process, the ball milling medium and the reaction material are subjected to the combined force of rotation and revolution in the ball mill, so that the centrifugal acceleration of the ball milling medium can reach 10-20g; at the same time, the pressure between the ball milling medium and the ball mill can reach 5-6 times of the weight of the ball milling medium itself. When the chitosan molecule is subjected to a strong mechanical force of the ball milling medium, the impact force and shear force of the chitosan particles will destroy the crystal structure in the molecule. During the ball milling alkalization process, sodium hydroxide can better enter the interior of the chitosan molecule, thereby achieving the effect of alkalization expansion. At the same time, during the carboxymethylation reaction, as the hydrogen bonds within and between chitosan molecules are broken by external mechanical force, the hydroxyl and amino groups within the chitosan molecules are exposed to the outside, thereby providing an attack target for the carboxymethyl groups in the system and promoting the occurrence of the carboxymethylation reaction.

[0086] In some optional examples, the mass ratio of the chitosan powder to sodium hydroxide is 1:(3.5~4.5), for example, it can be 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4.0, 1:4.1, 1:4.2, 1:4.3, 1:4.4 or 1:4.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0087] In some optional examples, the rotation speed of the primary ball milling is 500~600rpm, for example, it can be 500rpm, 510rpm, 520rpm, 530rpm, 540rpm, 550rpm, 560rpm, 570rpm, 580rpm, 590rpm or 600rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] In some optional examples, the time for the first ball milling is 4 to 5 hours, for example, it can be 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0089] In some optional examples, the mass ratio of the chitosan powder to sodium chloroacetate is 1:(3~4), for example, it can be 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9 or 1:4.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] The present invention particularly limits the mass ratio of chitosan powder and sodium chloroacetate to 1:(3-4), and with the increase of the sodium chloroacetate consumption, the substitution degree of the carboxymethyl functional group of the product presents a variation trend of first increasing and then decreasing. When the mass ratio of chitosan powder and sodium chloroacetate is within the numerical range defined by the present invention, with the increase of the sodium chloroacetate consumption, the probability of collision between the chitosan active center and the sodium chloroacetate increases, so that the carboxymethylation reaction is carried out in a positive direction, and therefore the substitution degree of the carboxymethyl functional group of the product is gradually improved. When the consumption of sodium chloroacetate exceeds the upper limit of the range defined by the present invention, excessive sodium chloroacetate consumes a part of sodium hydroxide, resulting in the occurrence of side reactions, reducing the utilization rate of sodium hydroxide, and causing the substitution degree of the carboxymethyl functional group of the product to decrease.

[0091] In some optional examples, the mass ratio of sodium chloroacetate to sodium iodide is 1:(0.5~0.7), for example, it can be 1:0.5, 1:0.52, 1:0.54, 1:0.56, 1:0.58, 1:0.6, 1:0.62, 1:0.64, 1:0.66, 1:0.68 or 1:0.7, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0092] In some optional examples, the rotation speed of the secondary ball milling is 500~600rpm, for example, it can be 500rpm, 510rpm, 520rpm, 530rpm, 540rpm, 550rpm, 560rpm, 570rpm, 580rpm, 590rpm or 600rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0093] The invention particularly limits the rotation speed of the secondary ball milling to 500-600 rpm, and as the rotation speed of the ball milling increases, the substitution degree of the carboxymethyl functional group of the product shows a trend of first increasing and then decreasing. When the rotation speed of the ball mill is within the range of 500-600 rpm, accelerating the rotation speed of the ball milling can increase the collision probability and the number of collisions of the chitosan powder, sodium hydroxide, sodium chloroacetate and sodium iodide, and when the mechanical force is large enough, the stress generated instantly by the chitosan powder far exceeds its mechanical strength, and then the powder particles are broken, the specific surface area is increased, the contact of the chitosan powder with the sodium hydroxide, sodium chloroacetate and sodium iodide is promoted, and the reaction rate of the carboxymethyl reaction is increased, so the substitution degree of the carboxymethyl functional group of the product is gradually increased. When the ball mill speed exceeds 600rpm, the excessively fast speed causes the contact time between the reaction materials and the ball milling medium to be too short. At the same time, the particle size of the chitosan powder cannot be further reduced after reaching the limit, and the tiny particles will agglomerate into secondary particles under the action of surface energy, van der Waals force and electrostatic force. When the ball mill speed exceeds 600rpm, the agglomeration rate of the tiny particles will exceed the generation rate of the tiny particles. At this time, a large number of secondary particles will be generated in the reaction system, resulting in a sharp decrease in the specific surface area of ​​the material and a rapid decrease in the reaction rate, which ultimately leads to a decrease in the degree of substitution of the carboxymethyl functional group of the product.

[0094] In some optional embodiments, the secondary ball milling time is 5 to 6 hours, for example, it can be 5.0h, 5.1h, 5.2h, 5.3h, 5.4h, 5.5h, 5.6h, 5.7h, 5.8h, 5.9h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0095] In some optional instances, the mass fraction of the hydrochloric acid solution is 8~10wt%, for example, it can be 8.0wt%, 8.2wt%, 8.4wt%, 8.6wt%, 8.8wt%, 9.0wt%, 9.2wt%, 9.4wt%, 9.6wt%, 9.8wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0096] As a preferred technical solution of the present invention, in step (III), the mass fraction of the carboxymethyl chitosan in the chitosan solution is 1-2wt%, for example, it can be 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2.0wt%, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0097] In some optional instances, the mass of the carboxymethyl chitosan is 25-30wt% of the total mass of the gelatin and the sodium carboxymethyl cellulose, for example, it can be 25wt%, 25.5wt%, 26wt%, 26.5wt%, 27wt%, 27.5wt%, 28wt%, 28.5wt%, 29wt%, 29.5wt% or 30wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0098] In the process of preparing double-layer microcapsule powder, carboxymethyl chitosan is introduced to strengthen the single-layer microcapsules in the prepolymer suspension, which not only optimizes the structural stability of the double-layer microcapsules, but also significantly improves its protection and sustained-release ability for curcumin. Among them, the amount of carboxymethyl chitosan has an important influence on the thermal stability of the double-layer microcapsule powder and the sustained-release effect of curcumin. The present invention can optimize the structural stability and sustained-release performance of the double-layer microcapsules by accurately controlling the amount of carboxymethyl chitosan, providing strong support for the protection and utilization of curcumin.

[0099] The present invention specifically limits the mass of carboxymethyl chitosan to 25-30wt% of the total mass of gelatin and sodium carboxymethyl cellulose. When the amount of carboxymethyl chitosan is controlled within this numerical range, the functional groups such as hydroxyl, amino and carboxymethyl on its molecular chain can form a good hydrogen bond network with gelatin and sodium carboxymethyl cellulose molecules, thereby enhancing the intermolecular force of the capsule wall material. This enhancement effect not only improves the mechanical strength of the capsule wall, but also significantly improves the thermal stability of the double-layer microcapsule powder. During the heating process, the dense capsule wall structure can effectively block the rapid transfer of heat, slow down the thermal decomposition rate of the curcumin wrapped in the capsule, thereby extending the thermal stability time of the double-layer microcapsule. In addition, an appropriate amount of carboxymethyl chitosan can not only strengthen the capsule wall structure, but also adjust the release rate of curcumin through its unique gel properties. There is an interaction force between the functional groups on the carboxymethyl chitosan molecular chain and the curcumin molecules, and this interaction can slow down the speed of curcumin diffusion from the capsule to the outside, thereby achieving a sustained release effect.

[0100] When the dosage of carboxymethyl chitosan is less than 25wt%, the cross-linking density of the capsule wall material is insufficient, and the capsule wall structure is relatively loose. This loose structure is prone to deformation and rupture when heated, causing the curcumin wrapped in the capsule to be exposed to the high temperature environment in advance, accelerating the thermal decomposition process. Therefore, too low a dosage of carboxymethyl chitosan will significantly reduce the thermal stability of the double-layer microcapsules. In addition, when the dosage of carboxymethyl chitosan is too low, the gel structure inside the capsule wall is not dense enough to effectively block the rapid diffusion of curcumin molecules. Curcumin will be released in large quantities in a short period of time, resulting in poor sustained release effect; at the same time, the loose capsule wall structure will also make it easier for harmful substances such as moisture and oxygen in the external environment to penetrate into the capsule, accelerating the degradation of curcumin.

[0101] On the contrary, when the amount of carboxymethyl chitosan exceeds 30wt%, although the cross-linking density of the capsule wall material is further increased, the excessive cross-linking degree will cause the capsule wall to become too rigid and brittle. This change not only reduces the flexibility of the capsule wall, but also increases the risk of cracking of the capsule wall when heated. In addition, excessive carboxymethyl chitosan may block the microporous structure inside the capsule wall, affecting the uniform distribution and loss of heat, and reducing the overall thermal stability of the double-layer microcapsules. In addition, when the amount of carboxymethyl chitosan is too high, the capsule wall structure becomes too dense, making it difficult for curcumin molecules to diffuse outward through the capsule wall. This slow release rate may not meet the demand for rapid release of curcumin in practical applications. At the same time, excessive carboxymethyl chitosan may also cause an imbalance in the osmotic pressure inside and outside the capsule wall, causing the capsule wall to swell or even rupture, affecting the stable release of curcumin.

[0102] In some optional examples, the mixing time of the prepolymer suspension and the chitosan solution is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0103] In some optional examples, the mass fraction of the alkali solution is 10~20wt%, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0104] In some optional embodiments, alkaline solution is added to the microcapsule solution to adjust its pH value to 5-6, for example, it can be 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9 or 6.0, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0105] In some optional instances, the mass of the tannic acid is 35-40wt% of the total mass of the gelatin, the sodium carboxymethyl cellulose and the carboxymethyl chitosan, for example, it can be 35wt%, 35.5wt%, 36wt%, 36.5wt%, 37wt%, 37.5wt%, 38wt%, 38.5wt%, 39wt%, 39.5wt% or 40wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0106] Tannic acid is a polyphenolic compound with multiple phenolic hydroxyl groups in its molecular structure. These phenolic hydroxyl groups can form hydrogen bonds and covalent bonds with amino, carboxyl and other functional groups in carboxymethyl chitosan molecules, thereby achieving cross-linking and curing. Through the cross-linking and curing of tannic acid, a tighter network structure is formed between carboxymethyl chitosan molecules, which not only enhances the mechanical strength of the capsule wall, but also improves its thermal stability.

[0107] The present invention specifically limits the mass of tannic acid to 35-40wt% of the total mass of gelatin, sodium carboxymethyl cellulose and carboxymethyl chitosan. When the amount of tannic acid is controlled within this numerical range, its cross-linking and curing effect is most significant. An appropriate amount of tannic acid can ensure that a uniform and dense cross-linking network is formed between carboxymethyl chitosan molecules. This network structure can effectively resist the transfer of heat and the thermal motion of molecules when heated, thereby slowing down the thermal decomposition rate of curcumin wrapped in the capsule. Therefore, an appropriate amount of tannic acid can significantly improve the thermal stability of the double-layer microcapsule powder. In addition, an appropriate amount of tannic acid can not only enhance the capsule wall structure, but also adjust the release rate of curcumin through its cross-linking and curing effect. The cross-linking network between the tannic acid molecules and the carboxymethyl chitosan molecules can form a dense barrier to effectively block the rapid diffusion of curcumin molecules. At the same time, the phenolic hydroxyl groups on the tannic acid molecules can also interact with the curcumin molecules to further slow down their release rate. Therefore, an appropriate amount of tannic acid can optimize the sustained release effect of the double-layer microcapsules on curcumin.

[0108] When the amount of tannic acid is less than 35wt%, its cross-linking and curing effect is insufficient, and a sufficiently dense capsule wall structure cannot be formed. The loose capsule wall is prone to deformation and collapse when heated, resulting in leakage of curcumin wrapped in the capsule, which accelerates the thermal decomposition process of curcumin. In addition, the loose capsule wall cannot effectively prevent the rapid diffusion of curcumin molecules, resulting in a too fast release rate of curcumin, which not only shortens the release time of curcumin, but also makes the local concentration too high, leading to adverse reactions or side effects. On the contrary, when the amount of tannic acid exceeds 40wt%, its cross-linking and curing effect is too strong, making the capsule wall structure too rigid and brittle, and more prone to cracking and breaking when heated, thereby reducing the overall thermal stability of the double-layer microcapsules; at the same time, excessive tannic acid may also block the microporous structure of the capsule wall, affecting the uniform distribution and loss of heat, further exacerbating the reduction of thermal stability. In addition, when the dosage of tannic acid is too high, the cross-linked network it forms is too dense, making it difficult for curcumin molecules to diffuse outward through the capsule wall, which in turn causes a significant decrease in the release rate of curcumin, and may even lead to a situation where the curcumin cannot be released.

[0109] In some optional examples, the mixing time of the microcapsule solution and the tannic acid is 3 to 4 hours, for example, 3.0 hours, 3.1 hours, 3.2 hours, 3.3 hours, 3.4 hours, 3.5 hours, 3.6 hours, 3.7 hours, 3.8 hours, 3.9 hours or 4.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0110] In some optional embodiments, the inlet air temperature of the spray drying is 130-150°C, for example, it can be 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, 142°C, 144°C, 146°C, 148°C or 150°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0111] In some optional embodiments, the outlet air temperature of the spray drying is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0112] In some optional examples, the air flow pressure of the spray drying is 0.6~0.7MPa, for example, it can be 0.6MPa, 0.61MPa, 0.62MPa, 0.63MPa, 0.64MPa, 0.65MPa, 0.66MPa, 0.67MPa, 0.68MPa, 0.69MPa or 0.7MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0113] As a preferred technical solution of the present invention, in step (IV), the weight proportions of the components in the mixed material are as follows:

[0114] Polylactic acid 70-75 parts;

[0115] 8-10 parts of quaternary ammonium sulfonated nanocellulose;

[0116] 15-20 parts of double-layer microcapsule powder;

[0117] 1~2 parts of plasticizer;

[0118] Lubricant 0.5~1.5 parts;

[0119] Antioxidant 0.1~0.5 parts.

[0120] Among them, the weight portion of polylactic acid can be 70 parts, 71 parts, 72 parts, 73 parts, 74 parts or 75 parts; the weight portion of quaternary ammonium sulfonated nanocellulose can be 8 parts, 8.2 parts, 8.4 parts, 8.6 parts, 8.8 parts, 9.0 parts, 9.2 parts, 9.4 parts, 9.6 parts, 9.8 parts or 10.0 parts; the weight portion of double-layer microcapsule powder can be 15 parts, 15.5 parts, 16 parts, 16.5 parts, 17 parts, 17.5 parts, 18 parts, 18.5 parts, 19 parts, 19.5 parts or 20 parts; the weight portion of plasticizer can be 1.0 parts, 1.1 parts, 1. The weight parts of the lubricant can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 or 1.5 parts; the weight parts of the antioxidant can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5 parts, but are not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0121] In some optional examples, the plasticizer includes any one of triacetin, tributyl citrate, dibutyl phthalate, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, acetyl tributyl citrate, epoxy soybean oil, propylene glycol adipate polyester, dioctyl maleate, polyethylene glycol or polyvinyl alcohol, or a combination of at least two thereof.

[0122] In some optional examples, the lubricant includes any one of paraffin, zinc stearate, calcium stearate, polyethylene wax, glyceryl monostearate or glyceryl distearate, or a combination of at least two thereof.

[0123] In some optional examples, the antioxidant includes any one of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant 1790, antioxidant DSTP, antioxidant 1098, antioxidant 168, and antioxidant 691, or a combination of at least two thereof.

[0124] As a preferred technical solution of the present invention, in step (IV), the melt extrusion process is carried out in a screw extruder, and the barrel of the screw extruder is divided into a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone, a seventh zone and an eighth zone with different temperatures along the material flow direction.

[0125] In some optional instances, the temperature of the first zone is 150-160°C, for example, it may be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0126] In some optional instances, the temperature of the second zone is 160-170°C, for example, it may be 160°C, 161°C, 162°C, 163°C, 164°C, 165°C, 166°C, 167°C, 168°C, 169°C or 170°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0127] In some optional instances, the temperature of the third zone is 170-180°C, for example, it may be 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 177°C, 178°C, 179°C or 180°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0128] In some optional instances, the temperature of the fourth zone is 175-185°C, for example, it can be 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C or 185°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0129] In some optional examples, the temperature of the fifth zone is 185-190°C, for example, it can be 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0130] In some optional examples, the temperature of the sixth zone is 190-195°C, for example, it can be 190°C, 191°C, 192°C, 193°C, 194°C or 195°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0131] In some optional examples, the temperature of the seventh zone is 200-205°C, for example, it can be 200°C, 201°C, 202°C, 203°C, 204°C or 205°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0132] In some optional examples, the temperature of the eighth zone is 195-200°C, for example, it can be 195°C, 196°C, 197°C, 198°C, 199°C or 200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0133] In some optional instances, the head temperature of the screw extruder is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0134] In some optional examples, the screw speed of the screw extruder is 200~300rpm, for example, it can be 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm or 300rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0135] In some optional examples, in step (IV), the film blowing process is carried out in a film blowing machine, and the interior of the barrel of the film blowing machine is divided into a ninth zone, a tenth zone, an eleventh zone, a twelfth zone and a thirteenth zone with different temperatures along the material flow direction.

[0136] In some optional instances, the temperature of the ninth zone is 175-185°C, for example, it can be 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C or 185°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0137] In some optional instances, the temperature of the tenth zone is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0138] In some optional instances, the temperature of the eleventh zone is 185-195°C, for example, it can be 185°C, 186°C, 187°C, 188°C, 189°C, 190°C, 191°C, 192°C, 193°C, 194°C or 195°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0139] In some optional instances, the temperature of the twelfth zone is 195-205°C, for example, it can be 195°C, 196°C, 197°C, 198°C, 199°C, 200°C, 201°C, 202°C, 203°C, 204°C or 205°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0140] In some optional instances, the temperature of the thirteenth zone is 190-200°C, for example, it can be 190°C, 191°C, 192°C, 193°C, 194°C, 195°C, 196°C, 197°C, 198°C, 199°C or 200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0141] In some optional examples, the screw speed of the film blowing machine is 100~200rpm, for example, it can be 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm or 200rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0142] In some optional examples, the traction speed of the film blowing machine is 5~10m / min, for example, it can be 5.0m / min, 5.5m / min, 6.0m / min, 6.5m / min, 7.0m / min, 7.5m / min, 8.0m / min, 8.5m / min, 9.0m / min, 9.5m / min or 10.0m / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0143] In some optional examples, the blowing ratio of the film blowing machine is 2 to 5, for example, 2, 3, 4 or 5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0144] In a second aspect, the present invention provides a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables, which is prepared by the preparation method described in the first aspect, wherein the sustained-release antibacterial enhanced composite film comprises polylactic acid, quaternary ammonium sulfonated nanocellulose, double-layer microcapsule powder, a plasticizer, a lubricant and an antioxidant.

[0145] Compared with the prior art, the present invention has the following beneficial effects:

[0146] The sustained-release antibacterial enhanced composite film prepared by the present invention has excellent barrier properties, antibacterial properties and mechanical properties, and has great application potential in the field of fruit and vegetable preservation. First, the present invention improves the dispersibility and compatibility of nanocellulose in the polymer matrix by sulfonation and quaternization modification, thereby enhancing the mechanical properties and barrier properties of the composite film. Subsequently, the present invention uses curcumin as the core material and gelatin and sodium carboxymethyl cellulose as the wall material to prepare a single-layer microcapsule with a core-shell structure, and then uses carboxymethyl chitosan to perform secondary coating and reinforcement on the single-layer microcapsule, and utilizes electrostatic action and intermolecular force to form a carboxymethyl chitosan protective layer on the surface of the single-layer microcapsule, which can increase the film thickness on the surface of curcumin to better resist external adverse factors and reduce the environmental sensitivity of the double-layer microcapsule. Finally, quaternary ammonium sulfonated nanocellulose and double-layer microcapsule powder were added to the polylactic acid matrix, and a composite film was obtained after melt extrusion, cooling, pelletizing and film blowing. The synergistic effect of quaternary ammonium sulfonated nanocellulose and double-layer microcapsule powder significantly improved the barrier properties, antibacterial properties and mechanical properties of the composite film. BRIEF DESCRIPTION OF THE DRAWINGS

[0147] Figure 1 A flow chart of the preparation process of the sustained-release antibacterial enhanced composite film provided in Examples 1-5 of the present invention;

[0148] Figure 2 The infrared spectra of nanocellulose, sulfonated nanocellulose prepared in Example 1 of the present invention and quaternary ammonium sulfonated nanocellulose;

[0149] Figure 3 zeta potential diagrams of nanocellulose, sulfonated nanocellulose prepared in Example 1 of the present invention, and quaternary ammonium sulfonated nanocellulose;

[0150] Figure 4 The infrared spectra of gelatin, sodium carboxymethyl cellulose, carboxymethyl chitosan prepared in Example 1 of the present invention, prepolymer suspension and double-layer microcapsule powder;

[0151] Figure 5 This is an optical micrograph of the prepolymer suspension prepared in Example 1 of the present invention;

[0152] Figure 6 This is an optical micrograph of the double-layer microcapsule powder prepared in Example 1 of the present invention;

[0153] Figure 7 This is a scanning electron microscope image of the prepolymer suspension prepared in Example 1 of the present invention;

[0154] Figure 8 This is a scanning electron microscope image of the double-layer microcapsule powder prepared in Example 1 of the present invention;

[0155] Fig. 9 This is a laser confocal micrograph of the prepolymer suspension prepared in Example 1 of the present invention;

[0156] Fig.10 This is a laser confocal micrograph of the double-layer microcapsule powder prepared in Example 1 of the present invention;

[0157] Fig.11 This is the curcumin sustained-release curve of the double-layer microcapsule powder prepared in Example 1 of the present invention;

[0158] Fig.12 This is a colony diagram obtained in the antibacterial performance test of Escherichia coli of the composite film prepared in the comparative example of the present invention;

[0159] Fig.13 This is a colony diagram obtained in the antibacterial performance test of Escherichia coli of the composite film prepared in Example 1 of the present invention;

[0160] Fig.14 This is a colony diagram obtained in a test of the antibacterial performance of Staphylococcus aureus of the composite film prepared in the comparative example of the present invention;

[0161] Fig.15 This is a colony diagram obtained in the antibacterial performance test of the composite film prepared in Example 1 of the present invention on Staphylococcus aureus;

[0162] Fig.16 The actual photos are taken of the composite films prepared in Example 1 of the present invention and the comparative example in the spinach preservation experiment;

[0163] Fig.17 These are actual photos of the composite films prepared in Example 1 of the present invention and the comparative example taken in a strawberry preservation experiment. DETAILED DESCRIPTION

[0164] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0165] Example 1

[0166] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables, such as Figure 1As shown, the preparation method specifically comprises the following steps:

[0167] (1) Add nanocellulose powder to a sodium hydroxide solution with a mass fraction of 5 wt% (the ratio of nanocellulose powder to sodium hydroxide solution is 1 g:50 mL), and ultrasonically disperse the nanocellulose at an ultrasonic power of 300 W for 40 min to obtain a nanocellulose dispersion. The nanocellulose dispersion is then mixed and stirred at 50 °C for 5 h to obtain a nanocellulose suspension. Dissolve 1,3-propane sultone in dimethyl sulfoxide to obtain a 1,3-propane sultone solution with a mass fraction of 4 wt%, and add the mixture to the nanocellulose suspension. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.14, the mixture was mixed and stirred at 60°C for 6 hours, and a reaction product was obtained after the reaction was completed. A 5wt% hydrochloric acid solution was dripped into the reaction product to adjust its pH value to 2, and then the reaction product was dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 10000Da. After the dialysis was completed, the dialyzed product was placed at -60°C for freeze-drying for 12 hours to obtain sulfonated nanocellulose;

[0168] The sulfonated nanocellulose was added to isopropanol in a ratio of 1 g:30 mL, and then ultrasonically dispersed for 40 min at an ultrasonic power of 300 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 0.5 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.2, and mixed and stirred at 60° C. for 4 h, and then heating was stopped, and mixed and stirred at room temperature for 15 h to obtain a reaction product, and then the reaction product was dialyzed for 5 days using a dialysis bag with a molecular weight cutoff of 10000 Da, and after the dialysis, the dialyzed product was freeze-dried at -40° C. for 24 h to obtain quaternary ammonium sulfonated nanocellulose;

[0169] (2) Add gelatin and sodium carboxymethyl cellulose to deionized water in a mass ratio of 6:1, mix and stir at 40°C for 2 h to obtain a wall material solution, in which the concentrations of gelatin and sodium carboxymethyl cellulose in the wall material solution are 15 g / L, add curcumin to the wall material solution to obtain a prepolymer solution, in which the mass ratio of the total mass of gelatin and sodium carboxymethyl cellulose to the mass of curcumin is 4:1; emulsify the prepolymer solution at a speed of 8000 rpm for 5 min, and after emulsification, add acetic acid dropwise to the prepolymer solution at a stirring speed of 300 rpm and a water bath heating condition of 40°C to adjust its pH value to 4, and then cool in an ice water bath at 5°C for 1 h, and continue to mix and stir for 20 min after cooling to obtain a prepolymer suspension;

[0170] (3) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:3.5, and ball-milled at a speed of 500 rpm for 5 h to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.5, and ball-milled for a second time at a speed of 500 rpm for 6 h to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 8 wt % was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain carboxymethyl chitosan;

[0171] Dispersing carboxymethyl chitosan in acetic acid solution, wherein the mass fraction of acetic acid in the acetic acid solution is 5wt%, and mixing evenly to obtain a chitosan solution, wherein the mass fraction of carboxymethyl chitosan in the chitosan solution is 1wt%, adding the chitosan solution to the prepolymer suspension, wherein the mass of carboxymethyl chitosan is 25wt% of the total mass of gelatin and sodium carboxymethyl cellulose, and mixing and stirring for 30min to obtain a microcapsule solution, adding a sodium hydroxide solution with a mass fraction of 10wt% to the microcapsule solution to adjust its pH value to 5, and then adding tannic acid to the microcapsule solution, wherein the mass of tannic acid is 35wt% of the total mass of gelatin, sodium carboxymethyl cellulose and carboxymethyl chitosan, and mixing and stirring for 3h to obtain a microcapsule suspension, spray drying the microcapsule suspension, wherein the inlet air temperature of the spray drying is 130°C, the outlet air temperature is 70°C, and the air flow pressure is 0.6MPa, and a double-layer microcapsule powder is obtained after spray drying;

[0172] (4) 70% of polylactic acid, 8% of quaternary ammonium sulfonated nanocellulose obtained in step (1), 20% of double-layer microcapsule powder obtained in step (3), 1% of ethylene glycol, 0.5% of calcium fatty acid and 0.5% of antioxidant 1010 are uniformly mixed to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 150°C, the temperature of the second zone is 160°C, the temperature of the third zone is 170°C, the temperature of the fourth zone is 175°C, the temperature of the fifth zone is 185°C, the temperature of the sixth zone is 190°C, the temperature of the seventh zone is 200°C, the temperature of the eighth zone is 195°C, the temperature of the die head is 180°C, and the screw speed is 200 rpm;

[0173] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 175°C, the temperature of the tenth zone is 180°C, the temperature of the eleventh zone is 185°C, the temperature of the twelfth zone is 195°C, and the temperature of the thirteenth zone is 190°C. The screw speed of the film blowing machine is 100rpm, the traction speed of the film blowing machine is 5m / min, and the blowing ratio of the film blowing machine is 2. After film blowing, the sustained-release antibacterial enhanced composite film is obtained.

[0174] Figure 2 The infrared spectra of nanocellulose, sulfonated nanocellulose prepared in this example, and quaternary ammonium sulfonated nanocellulose are shown in Figure 1. In the infrared spectrum curve of nanocellulose, 3284 cm -1 The corresponding OH stretching vibration absorption peak is 1038 cm -1 The corresponding absorption peak is the stretching vibration of CO.

[0175] In the infrared spectrum of sulfonated nanocellulose, 1375 cm -1 and 896cm -1 The stretching vibration absorption peaks corresponding to O=S=O and COS of the sulfonic acid functional group respectively indicate that the sulfonic acid functional group is successfully connected to the molecular chain of nanocellulose.

[0176] In the infrared spectrum curve of quaternary ammonium sulfonated nanocellulose, the stretching vibration absorption peak of OH is from 3284 cm -1 Offset to 3359cm -1 This is because the electrostatic effect of the introduced quaternary ammonium functional groups changes the forces between hydrogen bonds in nanocellulose. In addition, 2905cm -1 and 2846cm -1 The asymmetric stretching vibration and symmetric stretching vibration absorption peaks of -CH2- in the octadecyltrimethylammonium chloride molecular chain are 1443 cm -1The corresponding peak is the stretching vibration absorption peak of the trimethyl functional group in the molecular chain of octadecyltrimethylammonium chloride, which indicates that octadecyltrimethylammonium chloride is successfully connected to the molecular chain of sulfonated nanocellulose.

[0177] Figure 3 The zeta potential diagram of nanocellulose, sulfonated nanocellulose prepared in this embodiment and quaternary ammonium sulfonated nanocellulose is shown in the figure. It can be seen that the surface charge of nanocellulose is -5.8mV, and the surface charge of sulfonated nanocellulose obtained after sulfonation modification is -11.5mV, which is due to the fact that more anionic sites are combined on the surface of nanocellulose after sulfonation modification. The surface charge of quaternary ammonium sulfonated nanocellulose obtained after quaternary ammonium modification is -2.7mV, which is due to the negative charge on the surface of sulfonated nanocellulose being neutralized by the positive charge of quaternary ammonium salt.

[0178] Figure 4 The infrared spectra of gelatin, sodium carboxymethyl cellulose, carboxymethyl chitosan, prepolymer suspension and double-layer microcapsule powder are shown in Figure 1. In the infrared curve of gelatin, 1553 cm -1 Corresponding to -NH3 + Stretching vibration absorption peak. In the infrared curve of sodium carboxymethyl cellulose, 3430cm -1 The stretching vibration absorption peak corresponding to the hydrogen bond in the sodium carboxymethyl cellulose molecule is 2925cm -1 The corresponding CH stretching vibration absorption peak is 1600 cm -1 and 1411cm -1 The symmetric and asymmetric stretching vibration absorption peaks of -COO- correspond to the absorption peaks at 1600 cm-1 and 1600 cm-2, respectively. -1 The absorption peak at 1553 cm -1 The absorption peaks at the same time disappeared, indicating that the -NH3 + The -COO- of sodium carboxymethylcellulose has an electrostatic interaction. In addition, gelatin has a -1 The absorption peak at 3346 cm -1 , indicating that hydrogen bonds are involved in the formation of the complex coacervate.

[0179] In the infrared curve of carboxymethyl chitosan, 3374 cm -1 The 2877cm -1 The corresponding CH stretching vibration absorption peak is 1079 cm -1The corresponding stretching vibration absorption peak of CO is at 3346 cm. By comparing the infrared curves of carboxymethyl chitosan, prepolymer suspension and double-layer microcapsule powder, it can be seen that after adding carboxymethyl chitosan, the amide I band (3346 cm -1 )、Amide II band (1531cm -1 ) and amide III band (1195 cm -1 ) were shifted to 3406cm of the double-layer microcapsule powder. -1 、1558cm -1 and 1199cm -1 , indicating that there is a hydrogen bonding interaction between carboxymethyl chitosan and the complex coacervate. In addition, the prepolymer suspension has a -1 With 1028cm -1 The absorption peaks at 2932 cm -1 With 1034cm -1 This is due to the electrostatic interaction between the amino group and the carbonyl group, which indicates that there is also an electrostatic attraction between carboxymethyl chitosan and the complex coacervate.

[0180] Figure 5 and Figure 6 The optical micrographs of the prepolymer suspension and the double-layer microcapsule powder prepared in this embodiment are shown respectively. It can be seen from the figures that both the single-layer microcapsule powder and the double-layer microcapsule powder in the prepolymer suspension maintain a good spherical dispersion state, but the particle size of the double-layer microcapsule powder is significantly larger than that of the single-layer microcapsule powder, and it can be clearly seen that a new coating layer is formed on the surface of the single-layer microcapsule powder, which is the carboxymethyl chitosan protective layer.

[0181] Figure 7 and Figure 8 The scanning electron microscope images of the prepolymer suspension and the double-layer microcapsule powder prepared in this example are shown respectively. It can be seen from the figure that the surface of the single-layer microcapsule powder in the prepolymer suspension is smooth and flat, while the surface of the double-layer microcapsule powder is rough, and a carboxymethyl chitosan protective layer is formed on the surface of the single-layer microcapsule powder.

[0182] Fig. 9 and Fig.10 They are laser confocal micrographs of the prepolymer suspension and the double-layer microcapsule powder prepared in this embodiment, respectively. The laser confocal microscope can detect the distribution of gelatin, sodium carboxymethyl cellulose and chitosan on the microcapsule wall. By comparison, it can be clearly seen that the outer layer of the double-layer microcapsule is covered with a coating, namely, the carboxymethyl chitosan protective layer.

[0183] The sustained release performance of the double-layer microcapsule powder prepared in this example was tested, and the specific test steps were as follows:

[0184] (1) Accurately weigh 5 mg of curcumin, dissolve it in 10 mL of anhydrous ethanol, and then dilute it with PBS solution to 50 mL. Use a pipette to take 0.25 mL, 1 mL, 2 mL, 3 mL, 4 mL, and 5 mL of the solution, respectively, dilute it with 20% ethanol-PBS solution and make up to 50 mL. Measure its absorbance at the maximum absorption wavelength of 425 nm and draw a standard curve for the curcumin solution.

[0185] (2) Take a certain mass of double-layer microcapsule powder m0 (g), measure the absorbance at 425 nm, and calculate the mass of curcumin m1 (g) according to the solution standard curve. The calculation formula of drug loading RDL (%) is as follows:

[0186]

[0187] (3) Take a certain mass of double-layer microcapsule powder (w0) and place it in a ground-mouth conical flask. Add a certain amount of PBS (pH = 7.4) solution into the conical flask. Measure the absorbance at 425nm at room temperature at regular intervals. Calculate the mass of curcumin w according to the solution standard curve. n , the cumulative release rate of curcumin R SF The calculation formula of (%) is as follows:

[0188]

[0189] The cumulative release rate of curcumin at different times was summarized and plotted, as shown in the following figure. Fig.11 The curcumin sustained-release curve of the double-layer microcapsule powder is shown. It can be seen from the figure that the double-layer microcapsule powder is continuously released within 24 hours and has an excellent antibacterial sustained-release effect.

[0190] Example 2

[0191] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0192] (1) Nanocellulose powder was added to a sodium hydroxide solution with a mass fraction of 6 wt % (the ratio of nanocellulose powder to sodium hydroxide solution was 1 g:52 mL), and ultrasonic dispersion was performed at an ultrasonic power of 320 W for 38 min to obtain a nanocellulose dispersion. The nanocellulose dispersion was then mixed and stirred at 52 ° C for 4.5 h to obtain a nanocellulose suspension. 1,3-Propane sultone was dissolved in dimethyl sulfoxide to obtain a 1,3-Propane sultone solution with a mass fraction of 4.2 wt %, and the nanocellulose suspension was added. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.142, and the mixture was mixed and stirred at 62°C for 5.8 hours. After the reaction was completed, a reaction product was obtained, and a hydrochloric acid solution with a mass fraction of 6wt% was dripped into the reaction product to adjust its pH value to 1.8. The reaction product was then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 12000Da. After the dialysis was completed, the dialyzed product was placed at -62°C for freeze-drying for 11 hours to obtain sulfonated nanocellulose;

[0193] The sulfonated nanocellulose was added to isopropanol in a ratio of 1 g:32 mL, and then ultrasonically dispersed for 38 min at an ultrasonic power of 320 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 0.8 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9.2, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.22, and mixed and stirred at 62° C. for 3.8 h, and then heating was stopped, and mixed and stirred at room temperature for 13 h to obtain a reaction product, and then the reaction product was dialyzed for 5 days using a dialysis bag with a molecular weight cutoff of 12000 Da, and after the dialysis, the dialyzed product was freeze-dried at -42° C. for 21 h to obtain quaternary ammonium sulfonated nanocellulose;

[0194] (2) Add gelatin and sodium carboxymethyl cellulose to deionized water in a mass ratio of 6.2:1, mix and stir at 42°C for 1.8h to obtain a wall material solution, in which the concentrations of gelatin and sodium carboxymethyl cellulose in the wall material solution are 16g / L, add curcumin to the wall material solution to obtain a prepolymer solution, in which the mass ratio of the total mass of gelatin and sodium carboxymethyl cellulose to the mass of curcumin is 4.2:1; emulsify the prepolymer solution at a speed of 8500rpm for 4.5min, and after emulsification, add acetic acid dropwise to the prepolymer solution at a stirring speed of 320rpm and a water bath heating condition of 42°C to adjust its pH value to 4.2, and then cool in an ice water bath at 8°C for 1.2h, and continue to mix and stir for 22min after cooling to obtain a prepolymer suspension;

[0195] (3) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:3.8, and ball-milled for 4.8 hours at a rotation speed of 520 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3.2, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.55, and ball-milled for a second time at a rotation speed of 520 rpm for 5.8 hours to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 8.5 wt % was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain carboxymethyl chitosan;

[0196] Disperse carboxymethyl chitosan in acetic acid solution, wherein the mass fraction of acetic acid in the acetic acid solution is 5wt%, and mix well to obtain chitosan solution, wherein the mass fraction of carboxymethyl chitosan in the chitosan solution is 1.2wt%, add chitosan solution to prepolymer suspension, wherein the mass of carboxymethyl chitosan is 26wt% of the total mass of gelatin and sodium carboxymethyl cellulose, and mix and stir for 32min to obtain microcapsule solution, add sodium hydroxide solution with a mass fraction of 12wt% to the microcapsule solution to adjust its pH value to 5.2, then add tannic acid to the microcapsule solution, wherein the mass of tannic acid is 36wt% of the total mass of gelatin, sodium carboxymethyl cellulose and carboxymethyl chitosan, and mix and stir for 3.2h to obtain microcapsule suspension, spray dry the microcapsule suspension, wherein the inlet air temperature of the spray drying is 135°C, the outlet air temperature is 72°C, and the air flow pressure is 0.62MPa, and double-layer microcapsule powder is obtained after spray drying;

[0197] (4) 71 parts of polylactic acid, 10 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 15 parts of double-layer microcapsule powder obtained in step (3), 2 parts of epoxidized soybean oil, 1.5 parts of paraffin wax and 0.5 parts of antioxidant 1076 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 152° C., the temperature of the second zone is 162° C., the temperature of the third zone is 172° C., the temperature of the fourth zone is 178° C., the temperature of the fifth zone is 186° C., the temperature of the sixth zone is 191° C., the temperature of the seventh zone is 201° C., the temperature of the eighth zone is 196° C., the temperature of the die head is 182° C., and the screw speed is 220 rpm;

[0198] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 178°C, the temperature of the tenth zone is 182°C, the temperature of the eleventh zone is 188°C, the temperature of the twelfth zone is 198°C, and the temperature of the thirteenth zone is 192°C. The screw speed of the film blowing machine is 120rpm, the traction speed of the film blowing machine is 6m / min, and the blowing ratio of the film blowing machine is 3. After film blowing, the sustained-release antibacterial enhanced composite film is obtained.

[0199] Example 3

[0200] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0201] (1) Add nanocellulose powder to a sodium hydroxide solution with a mass fraction of 7 wt % (the ratio of nanocellulose powder to sodium hydroxide solution is 1 g:55 mL), and ultrasonically disperse the nanocellulose powder for 35 min at an ultrasonic power of 350 W to obtain a nanocellulose dispersion. The nanocellulose dispersion is then mixed and stirred at 55 ° C for 4 h to obtain a nanocellulose suspension. Dissolve 1,3-propane sultone in dimethyl sulfoxide to obtain a 1,3-propane sultone solution with a mass fraction of 4.5 wt %. Add the nanocellulose suspension to the solution. 1,3-propane sultone solution was added, the mass ratio of nanocellulose powder in the nanocellulose suspension to 1,3-propane sultone was 1:0.145, and the mixture was mixed and stirred at 65°C for 5.5 hours. After the reaction was completed, a reaction product was obtained, and a hydrochloric acid solution with a mass fraction of 7wt% was dripped into the reaction product to adjust its pH value to 1.5. The reaction product was then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 15000Da. After the dialysis was completed, the dialyzed product was placed at -65°C for freeze-drying for 10 hours to obtain sulfonated nanocellulose;

[0202] The sulfonated nanocellulose was added to isopropanol in a ratio of 1 g:35 mL, and then ultrasonically dispersed for 35 min at an ultrasonic power of 350 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 1 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9.5, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.25, and mixed and stirred at 65° C. for 3.5 h, and then heating was stopped, and mixed and stirred at room temperature for 12 h to obtain a reaction product, and then the reaction product was dialyzed for 6 days using a dialysis bag with a molecular weight cutoff of 15000 Da, and after the dialysis, the dialyzed product was freeze-dried at -45° C. for 18 h to obtain quaternary ammonium sulfonated nanocellulose;

[0203] (2) Add gelatin and sodium carboxymethyl cellulose to deionized water in a mass ratio of 6.5:1, mix and stir at 45°C for 1.5 hours to obtain a wall material solution, in which the concentrations of gelatin and sodium carboxymethyl cellulose in the wall material solution are 17 g / L, add curcumin to the wall material solution to obtain a prepolymer solution, in which the mass ratio of the total mass of gelatin and sodium carboxymethyl cellulose to the mass of curcumin is 4.5:1; emulsify the prepolymer solution at a speed of 9000 rpm for 4 minutes, and after emulsification, add acetic acid dropwise to the prepolymer solution at a stirring speed of 350 rpm and a water bath heating condition of 45°C to adjust its pH value to 4.5, and then cool in an ice water bath at 10°C for 1.5 hours, and continue to mix and stir for 25 minutes after cooling to obtain a prepolymer suspension;

[0204] (3) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:4, and ball-milled for 4.5 hours at a rotation speed of 550 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3.5, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.6, and ball-milled for a second time at a rotation speed of 550 rpm for 5.5 hours to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 9 wt % was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain carboxymethyl chitosan;

[0205] Dispersing carboxymethyl chitosan in acetic acid solution, wherein the mass fraction of acetic acid in the acetic acid solution is 5wt%, and mixing evenly to obtain a chitosan solution, wherein the mass fraction of carboxymethyl chitosan in the chitosan solution is 1.5wt%, adding the chitosan solution to the prepolymer suspension, wherein the mass of carboxymethyl chitosan is 27wt% of the total mass of gelatin and sodium carboxymethyl cellulose, and mixing and stirring for 35min to obtain a microcapsule solution, adding a sodium hydroxide solution with a mass fraction of 15wt% to the microcapsule solution to adjust its pH value to 5.5, and then adding tannic acid to the microcapsule solution, wherein the mass of tannic acid is 37wt% of the total mass of gelatin, sodium carboxymethyl cellulose and carboxymethyl chitosan, and mixing and stirring for 3.5h to obtain a microcapsule suspension, spray drying the microcapsule suspension, wherein the inlet air temperature of the spray drying is 140°C, the outlet air temperature is 75°C, and the air flow pressure is 0.65MPa, and a double-layer microcapsule powder is obtained after spray drying;

[0206] (4) 72 parts of polylactic acid, 9 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 16 parts of double-layer microcapsule powder obtained in step (3), 2 parts of pentaerythritol, 0.5 parts of glyceryl monostearate and 0.5 parts of antioxidant DSTP are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 155° C., the temperature of the second zone is 165° C., the temperature of the third zone is 175° C., the temperature of the fourth zone is 180° C., the temperature of the fifth zone is 187° C., the temperature of the sixth zone is 192° C., the temperature of the seventh zone is 202° C., the temperature of the eighth zone is 197° C., the temperature of the die head is 185° C., and the screw speed is 250 rpm;

[0207] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 180°C, the temperature of the tenth zone is 185°C, the temperature of the eleventh zone is 190°C, the temperature of the twelfth zone is 200°C, and the temperature of the thirteenth zone is 195°C. The screw speed of the film blowing machine is 150rpm, the traction speed of the film blowing machine is 7m / min, and the blowing ratio of the film blowing machine is 3. After film blowing, the sustained-release antibacterial enhanced composite film is obtained.

[0208] Example 4

[0209] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0210] (1) Nanocellulose powder was added to a sodium hydroxide solution with a mass fraction of 8 wt % (the ratio of nanocellulose powder to sodium hydroxide solution was 1 g:58 mL), and ultrasonic dispersion was performed at an ultrasonic power of 380 W for 32 min to obtain a nanocellulose dispersion. The nanocellulose dispersion was then mixed and stirred at 58 ° C for 3.5 h to obtain a nanocellulose suspension. 1,3-Propane sultone was dissolved in dimethyl sulfoxide to obtain a 1,3-Propane sultone solution with a mass fraction of 4.8 wt %, and the nanocellulose suspension was added thereto. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.148, the mixture was mixed and stirred at 68°C for 5.2h, and a reaction product was obtained after the reaction was completed. A hydrochloric acid solution with a mass fraction of 8wt% was dripped into the reaction product to adjust the pH value thereof to 1.2, and then the reaction product was dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 18000Da. After the dialysis was completed, the dialyzed product was placed at -68°C for freeze-drying for 8h to obtain sulfonated nanocellulose;

[0211] The sulfonated nanocellulose was added to isopropanol in a ratio of 1 g:38 mL, and then ultrasonically dispersed for 32 min at an ultrasonic power of 380 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 1.2 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9.8, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.28, and mixed and stirred at 68° C. for 3.2 h, and then heating was stopped, and mixed and stirred at room temperature for 11 h to obtain a reaction product, and then the reaction product was dialyzed for 7 days using a dialysis bag with a molecular weight cutoff of 18000 Da, and after the dialysis, the dialyzed product was freeze-dried at -48° C. for 15 h to obtain quaternary ammonium sulfonated nanocellulose;

[0212] (2) Add gelatin and sodium carboxymethyl cellulose to deionized water in a mass ratio of 6.8:1, mix and stir at 48°C for 1.2h to obtain a wall material solution, in which the concentrations of gelatin and sodium carboxymethyl cellulose in the wall material solution are 18g / L, add curcumin to the wall material solution to obtain a prepolymer solution, in which the mass ratio of the total mass of gelatin and sodium carboxymethyl cellulose to the mass of curcumin is 4.8:1; emulsify the prepolymer solution at a speed of 9500rpm for 3.5min, and after emulsification, add acetic acid to the prepolymer solution at a stirring speed of 380rpm and a water bath heating condition of 48°C to adjust its pH value to 4.8, and then cool in an ice water bath at 12°C for 1.8h, and continue to mix and stir for 28min after cooling to obtain a prepolymer suspension;

[0213] (3) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:4.2, and ball-milled for 4.2 h at a rotation speed of 580 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3.8, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.65, and ball-milled for a second time at a rotation speed of 580 rpm for 5.2 h to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 9.5 wt % was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain carboxymethyl chitosan;

[0214] Dispersing carboxymethyl chitosan in acetic acid solution, wherein the mass fraction of acetic acid in the acetic acid solution is 5wt%, and mixing evenly to obtain a chitosan solution, wherein the mass fraction of carboxymethyl chitosan in the chitosan solution is 1.8wt%, adding the chitosan solution to the prepolymer suspension, wherein the mass of carboxymethyl chitosan is 28wt% of the total mass of gelatin and sodium carboxymethyl cellulose, and mixing and stirring for 38min to obtain a microcapsule solution, adding a sodium hydroxide solution with a mass fraction of 18wt% to the microcapsule solution to adjust its pH value to 5.8, and then adding tannic acid to the microcapsule solution, wherein the mass of tannic acid is 38wt% of the total mass of gelatin, sodium carboxymethyl cellulose and carboxymethyl chitosan, and mixing and stirring for 3.8h to obtain a microcapsule suspension, spray drying the microcapsule suspension, wherein the inlet air temperature of the spray drying is 145°C, the outlet air temperature is 78°C, and the air flow pressure is 0.68MPa, and a double-layer microcapsule powder is obtained after spray drying;

[0215] (4) 73 parts of polylactic acid, 8 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 16 parts of double-layer microcapsule powder obtained in step (3), 2 parts of polyvinyl alcohol, 0.8 parts of distearic acid glyceryl and 0.2 parts of antioxidant 168 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 158° C., the temperature of the second zone is 168° C., the temperature of the third zone is 178° C., the temperature of the fourth zone is 182° C., the temperature of the fifth zone is 188° C., the temperature of the sixth zone is 193° C., the temperature of the seventh zone is 203° C., the temperature of the eighth zone is 198° C., the temperature of the die head is 188° C., and the screw speed is 280 rpm;

[0216] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 182°C, the temperature of the tenth zone is 188°C, the temperature of the eleventh zone is 192°C, the temperature of the twelfth zone is 202°C, and the temperature of the thirteenth zone is 198°C. The screw speed of the film blowing machine is 180rpm, the traction speed of the film blowing machine is 8m / min, and the blowing ratio of the film blowing machine is 4. After film blowing, the sustained-release antibacterial enhanced composite film is obtained.

[0217] Example 5

[0218] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0219] (1) Add nanocellulose powder to a sodium hydroxide solution with a mass fraction of 10 wt % (the ratio of nanocellulose powder to sodium hydroxide solution is 1 g:60 mL), and ultrasonically disperse the nanocellulose at an ultrasonic power of 400 W for 30 min to obtain a nanocellulose dispersion. The nanocellulose dispersion is then mixed and stirred at 60 ° C for 3 h to obtain a nanocellulose suspension. Dissolve 1,3-propane sultone in dimethyl sulfoxide to obtain a 1,3-propane sultone solution with a mass fraction of 5 wt %. Add the nanocellulose suspension to the solution. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.15, the mixture was mixed and stirred at 70°C for 5 hours, and a reaction product was obtained after the reaction was completed. A 10wt% hydrochloric acid solution was dripped into the reaction product to adjust its pH value to 1, and then the reaction product was dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 20000Da. After the dialysis was completed, the dialyzed product was placed at -70°C for freeze-drying for 6 hours to obtain sulfonated nanocellulose;

[0220] The sulfonated nanocellulose was added to isopropanol in a ratio of 1 g:40 mL, and then ultrasonically dispersed for 30 min at an ultrasonic power of 400 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 1.5 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 10, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.3, and mixed and stirred at 70° C. for 3 h, and then heating was stopped, and mixed and stirred at room temperature for 10 h to obtain a reaction product, and then the reaction product was dialyzed for 8 days using a dialysis bag with a molecular weight cutoff of 20,000 Da, and after the dialysis, the dialyzed product was freeze-dried at -50° C. for 12 h to obtain quaternary ammonium sulfonated nanocellulose;

[0221] (2) Add gelatin and sodium carboxymethyl cellulose to deionized water in a mass ratio of 7:1, mix and stir at 50°C for 1 hour to obtain a wall material solution, in which the concentrations of gelatin and sodium carboxymethyl cellulose in the wall material solution are 20 g / L, add curcumin to the wall material solution to obtain a prepolymer solution, in which the mass ratio of the total mass of gelatin and sodium carboxymethyl cellulose to the mass of curcumin is 5:1; emulsify the prepolymer solution at a speed of 10000 rpm for 3 minutes, and after emulsification, add acetic acid to the prepolymer solution at a stirring speed of 400 rpm and a water bath heating condition of 50°C to adjust its pH value to 5, and then cool in an ice water bath at 15°C for 2 hours, and continue to mix and stir for 30 minutes after cooling to obtain a prepolymer suspension;

[0222] (3) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:4.5, and ball-milled at a speed of 600 rpm for 4 h to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:4, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.7, and ball-milled for a second time at a speed of 600 rpm for 5 h to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 10 wt% was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain carboxymethyl chitosan;

[0223] Dispersing carboxymethyl chitosan in acetic acid solution, wherein the mass fraction of acetic acid in the acetic acid solution is 5wt%, and mixing evenly to obtain a chitosan solution, wherein the mass fraction of carboxymethyl chitosan in the chitosan solution is 2wt%, adding the chitosan solution to the prepolymer suspension, wherein the mass of carboxymethyl chitosan is 30wt% of the total mass of gelatin and sodium carboxymethyl cellulose, and mixing and stirring for 40min to obtain a microcapsule solution, adding a sodium hydroxide solution with a mass fraction of 20wt% to the microcapsule solution to adjust its pH value to 6, and then adding tannic acid to the microcapsule solution, wherein the mass of tannic acid is 40wt% of the total mass of gelatin, sodium carboxymethyl cellulose and carboxymethyl chitosan, and mixing and stirring for 4h to obtain a microcapsule suspension, spray drying the microcapsule suspension, wherein the inlet air temperature of the spray drying is 150°C, the outlet air temperature is 80°C, and the air flow pressure is 0.7MPa, and a double-layer microcapsule powder is obtained after spray drying;

[0224] (4) 75 parts of polylactic acid, 8 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 15 parts of double-layer microcapsule powder obtained in step (3), 1 part of triacetin, 0.9 parts of zinc stearate and 0.1 parts of antioxidant 691 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 160°C, the temperature of the second zone is 170°C, the temperature of the third zone is 180°C, the temperature of the fourth zone is 185°C, the temperature of the fifth zone is 190°C, the temperature of the sixth zone is 195°C, the temperature of the seventh zone is 205°C, the temperature of the eighth zone is 200°C, the temperature of the die head is 190°C, and the screw speed is 300 rpm;

[0225] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 185°C, the temperature of the tenth zone is 190°C, the temperature of the eleventh zone is 195°C, the temperature of the twelfth zone is 205°C, and the temperature of the thirteenth zone is 200°C. The screw speed of the film blowing machine is 200rpm, the traction speed of the film blowing machine is 10m / min, and the blowing ratio of the film blowing machine is 5. After film blowing, the sustained-release antibacterial enhanced composite film is obtained.

[0226] Example 6

[0227] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (1), the mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension is adjusted to 1:0.1, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0228] Example 7

[0229] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (1), the mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension is adjusted to 1:0.4, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0230] Example 8

[0231] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (2), the mass ratio of gelatin to sodium carboxymethyl cellulose is adjusted to 5:1, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0232] Example 9

[0233] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (2), the mass ratio of gelatin to sodium carboxymethyl cellulose is adjusted to 8:1, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0234] Example 10

[0235] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (3), the mass of carboxymethyl chitosan is 20wt% of the total mass of gelatin and sodium carboxymethyl cellulose, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0236] Embodiment 11

[0237] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (3), the mass of carboxymethyl chitosan is 35wt% of the total mass of gelatin and sodium carboxymethyl cellulose, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0238] Example 12

[0239] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (3), the mass of tannic acid is 30wt% of the total mass of gelatin, sodium carboxymethyl cellulose and carboxymethyl chitosan, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0240] Embodiment 13

[0241] This embodiment provides a method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (3), the mass of tannic acid is 45 wt % of the total mass of gelatin, sodium carboxymethyl cellulose and carboxymethyl chitosan, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0242] Comparative Example

[0243] This comparative example provides a method for preparing a composite film. The difference from Example 1 is that steps (1) to (4) are omitted, quaternary ammonium sulfonated nanocellulose and double-layer microcapsule powder are not added to the mixed material, and the weight parts of the other components are as follows:

[0244] Polylactic acid 97 parts;

[0245] 1 part of ethylene glycol;

[0246] 1.5 parts of calcium stearate;

[0247] Antioxidant 10100.5 parts;

[0248] Other process parameters and operation steps are exactly the same as those in Example 1.

[0249] Application Examples

[0250] The composite films provided in Example 1 and the comparative example were used to carry out a fresh-keeping storage experiment on spinach. Two identical cartons were prepared, and the composite film provided in Example 1 was pasted on the inner wall of one of the cartons, and the composite film provided in the comparative example was pasted on the inner wall of the other cartons. Two handfuls of spinach of similar freshness and same weight were placed in the two cartons respectively and sealed, and stored at 5°C. The state of the spinach was observed and photographed every two days. Fig.16 As shown, by comparison, it can be seen that the use of the composite film provided in Example 1 of the present invention to preserve and store spinach can keep the spinach very fresh on the 8th day of storage, effectively inhibit the water loss of spinach, maintain the color of spinach, maintain its quality during storage, and extend the shelf life.

[0251] The composite films provided in Example 1 and the comparative example were used to carry out a fresh-keeping storage experiment on strawberries. Two identical cartons were prepared, and the composite film provided in Example 1 was pasted on the inner wall of one of the cartons, and the composite film provided in the comparative example was pasted on the inner wall of the other carton. Two strawberries of similar freshness and the same weight were placed in the two cartons respectively and sealed, and stored at 5°C. The state of the strawberries was observed and photographed every two days. Fig.17As shown, by comparison, it can be seen that the composite film provided in Example 1 of the present invention is used to preserve and store strawberries, so that the strawberries can still maintain a very high degree of freshness on the 7th day of storage, effectively inhibiting the strawberries from losing water, rotting and deteriorating, maintaining their quality during storage, and extending their shelf life.

[0252] The mechanical properties, barrier properties and antibacterial properties of the composite films prepared in Examples 1-13 and the comparative example were tested, and the testing method was as follows:

[0253] (1) Mechanical properties: The mechanical properties of the composite films were characterized by tensile strength and elongation at break. The tensile strength and elongation at break of the composite films provided in Examples 1 to 13 and the comparative example were measured using a tensile testing machine, and the tensile rate was set to 50 mm / min.

[0254] (2) Barrier property: The barrier property of the composite films provided in Examples 1-13 and the comparative example is characterized by water vapor permeability. The water vapor permeability is measured in a constant temperature and humidity chamber in accordance with GB / T1037-2021 "Determination of water vapor permeability of plastic films and sheets - cup weight gain and weight loss method". The experimental conditions are: temperature 38±0.6°C, relative humidity 90%±2%.

[0255] (3) Antibacterial properties:

[0256] The antibacterial properties of the composite films provided in Example 1 and the comparative example were analyzed by the antibacterial zone method. The composite films provided in Example 1 and the comparative example were first cut into discs with a diameter of 6 mm and uniform size. Then 100 μL of a 10 6 CFU / mL of Escherichia coli suspension (model D1125B, purchased from Shanghai Roadway Technology Co., Ltd., China) and Staphylococcus aureus suspension (model E2528B, purchased from Shanghai Roadway Technology Co., Ltd., China) were evenly spread on the surface of the nutrient agar medium plate. The cut film samples were placed on the surface of the nutrient agar medium plate coated with the bacterial solution, and then placed in a 37℃ constant temperature box for 24 hours. The size of the antibacterial zone around the film sample was observed and photographed and recorded, and the following was obtained: Fig.12 , Fig.13 , Fig.14 and Fig.15 Colony images are shown.

[0257] Fig.12 and Fig.13The colony images are respectively obtained from the antibacterial performance test of the composite films prepared in the comparative example and in Example 1. From the comparison, it can be seen that there is almost no antibacterial zone around the periphery of the composite film prepared in the comparative example, while there is an obvious antibacterial zone around the periphery of the composite film prepared in Example 1. After measurement, the diameter of the antibacterial zone is about 2.3 mm, which indicates that the composite film prepared in the present invention has excellent antibacterial ability against Escherichia coli.

[0258] Fig.14 and Fig.15 The colony images of the composite films prepared in the comparative example and Example 1 respectively obtained in the antibacterial performance test of Staphylococcus aureus. It can be seen from the comparison that there is almost no antibacterial zone around the composite film prepared in the comparative example, while there is an obvious antibacterial zone around the composite film prepared in Example 1. The measurement shows that the diameter of the antibacterial zone is about 2.0 mm, which indicates that the composite film prepared in the present invention has excellent antibacterial ability against Staphylococcus aureus.

[0259] (4) Antibacterial properties:

[0260] The antibacterial activity of the composite films provided in Examples 1-13 was analyzed by colony counting method. The composite films provided in Examples 1-13 and the comparative example were cut into 3 mm×3 mm square film samples. 100 μL of 10 6 CFU / mL of Escherichia coli suspension (model D1125B, purchased from Shanghai Roadway Technology Co., Ltd., China) and Staphylococcus aureus suspension (model E2528B, purchased from Shanghai Roadway Technology Co., Ltd., China) were dispersed on the surface of the film sample and cultured at 37°C for 12 hours to obtain the sample; then 1500μL of PBS solution was used to wash the bacteria from the sample surface, and 20μL of PBS solution was taken and dispersed on the nutrient agar plate, and cultured at 37°C for 12 hours, after which the surviving colonies were counted. The antibacterial rate (%) was calculated using the following formula:

[0261]

[0262] Wherein, X is the number of colonies on the composite film sample provided in the comparative example, and Y is the number of colonies on the composite film sample provided in Examples 1-13.

[0263] The test data is shown in Table 1.

[0264] Table 1

[0265]

[0266] It can be seen from the test data provided in Table 1 that the composite films provided in Examples 1-5 of the present invention have excellent mechanical properties, barrier properties and antibacterial properties.

[0267] It can be seen from the test data of Example 1, Example 6 and Example 7 that too high or too low an amount of octadecyltrimethylammonium chloride will directly affect the quaternization modification effect on nanocellulose, thereby affecting the mechanical properties, barrier properties and antibacterial properties of the composite film.

[0268] It can be seen from the test data of Example 1, Example 8 and Example 9 that too high or too low a dosage of gelatin will directly affect the structural stability of the double-layer microcapsule powder and the sustained-release effect of curcumin, thereby affecting the antibacterial properties of the composite film.

[0269] It can be seen from the test data of Example 1, Example 10 and Example 11 that excessive or low dosage of carboxymethyl chitosan will directly affect the structural stability of the double-layer microcapsule powder and the sustained-release effect of curcumin, thereby affecting the antibacterial properties of the composite film.

[0270] It can be seen from the test data of Example 1, Example 12 and Example 13 that too high or too low an amount of tannic acid will directly affect the structural stability of the double-layer microcapsule powder and the sustained-release effect of curcumin, thereby affecting the antibacterial properties of the composite film.

[0271] It can be seen from the test data of Example 1 and the comparative example that the present invention can significantly improve the barrier properties, mechanical properties and antibacterial properties of the composite film by adding quaternary ammonium sulfonated nanocellulose and double-layer microcapsule powder into the polymer matrix.

[0272] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a sustained-release antibacterial enhanced composite film for preserving fruits and vegetables, characterized in that: The preparation method comprises: (I) sulfonating and modifying nanocellulose powder with 1,3-propane sultone to obtain sulfonated nanocellulose; then quaternizing and modifying the sulfonated nanocellulose with octadecyltrimethylammonium chloride to obtain quaternary ammonium sulfonated nanocellulose; (II) adding gelatin and sodium carboxymethyl cellulose into deionized water, mixing, stirring and heating to obtain a wall material solution, adding curcumin to the wall material solution to obtain a prepolymer solution; subjecting the prepolymer solution to high-speed stirring and emulsification, then dropping an acetic acid solution into the prepolymer solution under stirring and water bath heating conditions to adjust the pH value thereof, and cooling in an ice water bath to obtain a prepolymer suspension; (III) dispersing carboxymethyl chitosan in an acetic acid solution to obtain a chitosan solution, adding the chitosan solution to the prepolymer suspension, mixing uniformly to obtain a microcapsule solution, adding an alkali solution to the microcapsule solution to adjust the pH value thereof, then adding tannic acid to the microcapsule solution, mixing uniformly to obtain a microcapsule suspension, and spray drying the microcapsule suspension to obtain a double-layer microcapsule powder; (IV) Polylactic acid, the quaternary ammonium sulfonated nanocellulose obtained in step (I), the double-layer microcapsule powder obtained in step (III), a plasticizer, a lubricant and an antioxidant are uniformly mixed to obtain a mixed material, and the mixed material is sequentially melt-extruded, cooled, pelletized and film-blown to obtain the sustained-release antibacterial enhanced composite film.

2. The preparation method according to claim 1, characterized in that: In step (I), the sulfonated nanocellulose is prepared by the following method: The nanocellulose powder is added to a sodium hydroxide solution, and a nanocellulose dispersion is obtained after ultrasonic dispersion, and then the nanocellulose dispersion is mixed, stirred and heated to obtain a nanocellulose suspension; a 1,3-propane sultone solution is added to the nanocellulose suspension, and the mixture is mixed, stirred and heated to react, and a reaction product is obtained after the reaction is completed, a hydrochloric acid solution is dripped into the reaction product to adjust the pH value thereof, and then the reaction product is dialyzed and freeze-dried to obtain the sulfonated nanocellulose; The mass fraction of the sodium hydroxide solution is 5-10wt%; The ratio of the nanocellulose powder to the sodium hydroxide solution is 1 g: (50-60) mL; The ultrasonic power of the ultrasonic dispersion of the nanocellulose powder and the sodium hydroxide solution is 300-400W; The ultrasonic dispersion time of the nanocellulose powder and the sodium hydroxide solution is 30 to 40 minutes; The mixing and stirring time of the nanocellulose dispersion is 3 to 5 hours; The heating temperature of the nanocellulose dispersion during mixing and stirring is 50-60°C; The 1,3-propane sultone solution consists of 1,3-propane sultone and dimethyl sulfoxide; The mass fraction of 1,3-propane sultone in the 1,3-propane sultone solution is 4-5wt%; The mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone is 1:(0.14-0.15); The mixing and stirring time of the nanocellulose suspension and the 1,3-propane sultone solution is 5 to 6 hours; The heating temperature when the nanocellulose suspension and the 1,3-propane sultone solution are mixed and stirred is 60-70° C.; The mass fraction of the hydrochloric acid solution is 5-10wt%; Adding hydrochloric acid solution dropwise into the reaction product to adjust the pH value thereof to 1-2; The molecular weight cut-off of the dialysis bag used in the dialysis is 10000~20000Da; The dialysis time is 2 to 3 days; The freeze drying temperature is -60 to -70°C; The freeze-drying time is 6 to 12 hours.

3. The preparation method according to claim 1, characterized in that: In step (I), the quaternary ammonium sulfonated nanocellulose is prepared by the following method: The sulfonated nanocellulose is added to isopropanol to obtain a sulfonated nanocellulose suspension after ultrasonic dispersion, an alkali solution is added dropwise to the sulfonated nanocellulose suspension to adjust its pH value, octadecyltrimethylammonium chloride is then added to the sulfonated nanocellulose suspension, mixed and stirred, and heated for a period of time, then the heating is stopped, and the mixing and stirring is continued at room temperature for a period of time to obtain a reaction product, and the reaction product is dialyzed and freeze-dried to obtain the quaternary ammonium sulfonated nanocellulose; The ratio of the sulfonated nanocellulose to isopropanol is 1 g: (30-40) mL; The ultrasonic power of the ultrasonic dispersion of the sulfonated nanocellulose and isopropanol is 300-400W; The ultrasonic dispersion time of the sulfonated nanocellulose and isopropanol is 30 to 40 minutes; The concentration of the alkali solution is 0.5-1.5 mol / L; Adding alkaline solution dropwise to the sulfonated nanocellulose suspension to adjust the pH value thereof to 9-10; The mass ratio of the sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension is 1:(0.2-0.3); The sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride are mixed and stirred under heating conditions for 3 to 4 hours; The heating temperature when the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride are mixed and stirred under heating conditions is 60-70° C.; The mixing and stirring time of the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride at room temperature is 10 to 15 hours; The molecular weight cut-off of the dialysis bag used in the dialysis is 10000~20000Da; The dialysis time is 5 to 8 days; The freeze drying temperature is -40 to -50°C; The freeze-drying time is 12 to 24 hours.

4. The preparation method according to claim 1, characterized in that: In step (II), the concentration of gelatin and sodium carboxymethyl cellulose in the wall material solution is 15-20 g / L; The mass ratio of the gelatin to the sodium carboxymethyl cellulose is (6-7):1; The mixing time is 1 to 2 hours; The heating temperature during the mixing and stirring is 40-50°C; The ratio of the total mass of gelatin and sodium carboxymethyl cellulose in the wall material solution to the mass of curcumin is (4-5):1; The stirring speed of the high-speed stirring emulsification of the prepolymer solution is 8000-10000 rpm; The high-speed stirring emulsification time of the prepolymer solution is 3 to 5 minutes; The stirring speed during the process of dripping the acetic acid solution is 300~400rpm; The water bath heating temperature during the process of dripping the acetic acid solution is 40~50℃; Adding the acetic acid solution dropwise into the prepolymer solution to adjust the pH value thereof to 4-5; The temperature of the ice water bath is 5-15°C; Cool in the ice water bath for 1 to 2 hours; After cooling, the mixture is mixed and stirred for 20 to 30 minutes to obtain the prepolymer suspension.

5. The preparation method according to claim 1, characterized in that: In step (III), the carboxymethyl chitosan is prepared by the following method: Mixing chitosan powder and sodium hydroxide and then ball-milling once to obtain a mixture, adding sodium chloroacetate and sodium iodide to the mixture, mixing and then ball-milling twice to obtain a solid product, mixing the solid product with deionized water to obtain a product solution, and adding hydrochloric acid solution to the product solution to adjust the pH value of the product solution to 7; Subsequently, the product solution is filtered, washed and dried to obtain the carboxymethyl chitosan; The mass ratio of the chitosan powder to sodium hydroxide is 1:(3.5-4.5); The rotation speed of the first ball mill is 500-600 rpm; The time of the first ball milling is 4 to 5 hours; The mass ratio of the chitosan powder to sodium chloroacetate is 1:(3-4); The mass ratio of the sodium chloroacetate to the sodium iodide is 1:(0.5-0.7); The rotation speed of the secondary ball milling is 500-600 rpm; The secondary ball milling time is 5 to 6 hours; The mass fraction of the hydrochloric acid solution is 8-10wt%.

6. The preparation method according to claim 1, characterized in that: In step (III), the mass fraction of the carboxymethyl chitosan in the chitosan solution is 1-2wt%; The mass of the carboxymethyl chitosan is 25-30wt% of the total mass of the gelatin and the sodium carboxymethyl cellulose; The mixing time of the prepolymer suspension and the chitosan solution is 30 to 40 minutes; The mass fraction of the alkali solution is 10-20wt%; Adding alkali solution to the microcapsule solution to adjust its pH value to 5-6; The mass of the tannic acid is 35-40wt% of the total mass of the gelatin, the sodium carboxymethyl cellulose and the carboxymethyl chitosan; The mixing time of the microcapsule solution and the tannic acid is 3 to 4 hours; The inlet air temperature of the spray drying is 130-150°C; The outlet air temperature of the spray drying is 70-80°C; The air flow pressure of the spray drying is 0.6-0.7 MPa.

7. The preparation method according to claim 1, characterized in that: In step (IV), the weight proportions of the components in the mixed material are as follows: Polylactic acid 70-75 parts; 8-10 parts of quaternary ammonium sulfonated nanocellulose; 15-20 parts of double-layer microcapsule powder; 1~2 parts of plasticizer; 0.5~1.5 parts of lubricant; Antioxidant 0.1~0.5 parts; The plasticizer includes any one of triacetin, tributyl citrate, dibutyl phthalate, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, acetyl tributyl citrate, epoxy soybean oil, propylene glycol adipate polyester, dioctyl maleate, polyethylene glycol or polyvinyl alcohol, or a combination of at least two thereof; The lubricant includes any one of paraffin, zinc stearate, calcium stearate, polyethylene wax, glyceryl monostearate or glyceryl distearate, or a combination of at least two thereof; The antioxidant includes any one of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant 1790, antioxidant DSTP, antioxidant 1098, antioxidant 168, and antioxidant 691, or a combination of at least two thereof.

8. The preparation method according to claim 1, characterized in that: In step (IV), the melt extrusion process is carried out in a screw extruder, and the barrel of the screw extruder is divided into a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone, a seventh zone and an eighth zone with different temperatures along the material flow direction; The temperature of the first zone is 150-160°C; The temperature of the second zone is 160-170°C; The temperature of the third zone is 170-180°C; The temperature of the fourth zone is 175-185°C; The temperature of the fifth zone is 185-190°C; The temperature of the sixth zone is 190-195°C; The temperature of the seventh zone is 200-205°C; The temperature of the eighth zone is 195-200°C; The head temperature of the screw extruder is 180-190°C; The screw speed of the screw extruder is 200-300 rpm.

9. The preparation method according to claim 1, characterized in that: In step (IV), the film blowing process is carried out in a film blowing machine, and the inside of the barrel of the film blowing machine is divided into a ninth zone, a tenth zone, an eleventh zone, a twelfth zone and a thirteenth zone with different temperatures along the material flow direction; The temperature of the ninth zone is 175-185°C; The temperature of the tenth zone is 180-190°C; The temperature of the eleventh zone is 185-195°C; The temperature of the twelfth zone is 195-205°C; The temperature of the thirteenth zone is 190-200°C; The screw speed of the film blowing machine is 100-200 rpm; The traction speed of the film blowing machine is 5-10 m / min; The blowing ratio of the film blowing machine is 2-5.

10. A sustained-release antibacterial enhanced composite film for preserving fruits and vegetables prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The sustained-release antibacterial enhanced composite film comprises polylactic acid, quaternary ammonium sulfonated nanocellulose, double-layer microcapsule powder, plasticizer, lubricant and antioxidant.

Citation Information

Patent Citations

  • Nano-antibacterial microcapsule, nano-antibacterial composite coating liquid containing nano-antibacterial microcapsule as well as preparation method and application of nano-antibacterial composite coating liquid

    CN117643314A

Cited By

  • Antibacterial wear-resistant cellosilk and preparation method thereof

    CN120330909A

  • Quick-frozen crisp-keeping bamboo shoots and production process thereof

    CN120391632A

  • Preparation method of anisaldehyde microcapsule / polyvinyl alcohol composite film applied to carrot preservation

    CN121021882A